Asymptotic solutions of transient waves generated by a wavemaker in water of uniform depth - Haiqi Fang; Peter H.-Y. Lo; Pengzhi Lin; Philip L.-F. Liu (Wave Motion, 2027)

Temporal changes in milk fat globule membrane proteins in bovine raw milk - Lin Ma; Bertram Y. Fong; Alastair K.H. MacGibbon (International Dairy Journal, 2026)

Effects of Lactobacillus- and Bacillus-based probiotics on growth performance, intestinal barrier function, and microbiota modulation in nursery pigs: A meta-analysis - K. Sahatsanon; A. Jayanegara; S.W. Kim; Y. Ruangpanit; C.-S. Lin; P. Sivapirunthep; C. Chaosap (Animal Feed Science and Technology, 2026)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Erratum to “Extracellular polymeric substances in aerobic granular sludge under increasing salinity conditions” [Water Research (2026) 292/125313] - Le Min Chen; Sunanda Keisham; Hiroaki Tateno; Gijs Y. Kleine; Martin Pabst; Mario Pronk; Mark C.M. van Loosdrecht; Yuemei Lin (Water Research, 2026)

Functional polysaccharide-based bioactive delivery systems for urinary and reproductive system therapeutics - Yung-Wei Lin; Lekshmi Rethi; Wen-Yu Pan; Hieu Trung Nguyen; Andrew E.-Y. Chuang (Drug Delivery and Translational Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Application of a novel complex surfactant to enhance the bioremediation of weathered-diesel oil contaminated soils: mechanism and mesocosm-scale study - Wei-Ting Chen; Jiun-Hau Ou; Wei-Zhe Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Soils and Sediments, 2026)

Correction: Quantifying the effectiveness of superposed roughness elements to reduce dust emissions at the Salton Sea using computational fluid dynamics simulations - E. Furtak-Cole; J. A. Gillies; G. Nikolich; Y. Lin; S. Roy; J. Harrington (Air Quality, Atmosphere & Health, 2026)

Corrigendum to “Virus-induced redox cycling in Fe(II)/peracetic acid systems: dual roles as reactant and catalytic promoter” [Water Research 289 (2026) 124920] - Xiao Liu; An Ding; Wei Lin; Wei Qiu; Geoffroy Lesage; Marc Heran; Yan Zhao; Chuyang Y. Tang (Water Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Flocculation dynamics of suspended particulate matter under various tidal conditions - Mingze Lin; Xiaoteng Shen; Changjian Xu; Michael Fettweis; Byung Joon Lee; Qilong Bi; Peter Robins; Xiaorong Li; Jerome P.-Y. Maa; Gang Wang (Journal of Hydrology, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Extracellular polymeric substances in aerobic granular sludge under increasing salinity conditions - Le Min Chen; Sunanda Keisham; Hiroaki Tateno; Gijs Y. Kleine; Martin Pabst; Mario Pronk; Mark C.M. van Loosdrecht; Yuemei Lin (Water Research, 2026)

Plasmalogens in bovine raw milk, human milk and bovine MFGM isolates - Lin Ma; Bertram Y. Fong; Alastair K.H. MacGibbon (International Dairy Journal, 2026)

Prenatal urinary biomarkers of metal and metalloid exposure and child neurodevelopmental outcomes in Puerto Rico - Savannah M. Sturla Irizarry; Amber L. Cathey; Emily Zimmerman; Wei Hao; Yi-Ting Lin; Bhramar Mukherjee; Zaira Y. Rosario Pabón; Gredia Huerta Montañez; Carmen M. Vélez Vega; Akram N. Alshawabkeh; José F. Cordero; John D. Meeker; et al. (Environmental Research, 2026)

Cellular vesicle–electrically conducting polymer integrating with microalgae attenuate retinal inflammation associated with IL-6, immunomodulation, and pro-inflammatory cytokines in diabetes-related retinal disease - Andrew E.-Y. Chuang; Yo-Lin Chen; Chia-Hung Liu; Hieu Trung Nguyen; Tsung-Jen Wang; I-Chan Lin (Chemical Engineering Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Transportation-induced gentrification: new perspectives and evidence - Jen-Jia Lin; Karen Chapple; Sylvia Y. He; Tim Schwanen (Transportation Research Part D: Transport and Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Birds That Don't Exist: Niche Pre‐Emption as a Constraint on Morphological Evolution in the Passeroidea - Stephanie Y. Chia; Anshuman Swain; Nathaniel Josephs; Lizhen Lin; William F. Fagan (Ecology Letters, 2026)
Understanding why some viable body forms never evolve can reveal how ecological and evolutionary forces shape biodiversity. We investigate this question in the Passeroidea, a large group of songbirds, by analysing their morphological trait space using topological data analysis and ancestral state reconstruction. We identify a persistent morphological gap densely surrounded by extant species but unoccupied throughout passeroid diversification. The gap patterns deviate from stochastic expectations and show no evidence of past occupation, rendering undirected trait evolution and extinction unlikely. Similar morphologies exist in other bird lineages, ruling out intrinsic constraints or niche absence. Geographic distributions and traits of passeroids versus non‐passeroid gap occupants point to competitive exclusion as the plausible explanation: early‐colonising territorial specialists outside the Passeroidea may have preemptively occupied key habitats, limiting evolutionary opportunities for later‐arriving lineages. We demonstrate how historical contingency can shape macroevolutionary outcomes and introduce a generalizable framework for investigating structural gaps in trait evolution.

Virus-induced redox cycling in Fe(II)/peracetic acid systems: dual roles as reactant and catalytic promoter - Xiao Liu; An Ding; Wei Lin; Wei Qiu; Geoffroy Lesage; Marc Heran; Yan Zhao; Chuyang Y. Tang (Water Research, 2026)

Electrolytic hydrogen production from acidified wastewater effluent - Lin Du; Jinyue Jiang; Guangye Zhou; Yuqing Yan; Ryan S. Kingsbury; Anthony Y. Ku; Zhiyong Jason Ren (Water Research, 2026)

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)

A new model for the global patterning of spores and pollen grains - Kun L. Yang; Zhu L. Yang; Yang Luo; Jia Y. Lin; Hong Wang; Pan Meng Wang (Protoplasma, 2026)

Investigating the interaction of tropical cyclone-heatwave compound hazards in urban environments - Christine Y. Blackshaw; Ning Lin; Amirhosein Begmohammadi; Elie Bou-Zeid (Urban Climate, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Meta-analysis on microplastics monitoring in global water resource recovery facilities: An emphasis on overlooked factors - Elinor S. Austin; Dana M. Austin; Linda Y. Tseng; Lin Liu; Zeth Kleinmeyer; Danielle Drake; Diego Rosso; Yian Sun (Environmental Pollution, 2025)

Subcellular localization of the P2X4 receptor in sensory hair cells of Wistar rat cochlea - Ziyin Huang; Jacqueline M. Ross; Shelly C. Y. Lin; Prakansha N. Kumar; Kevin Roy; Srdjan M. Vlajkovic; Peter R. Thorne; Haruna Suzuki-Kerr (Histochemistry and Cell Biology, 2025)
Our sense of hearing starts in the inner ear organ, the cochlea, which contains two types of auditory hair cells for signal transduction. Earlier research showed that the complex cochlear physiology is regulated in part by purinergic signalling through activation of purine-mediated P2X, P2Y and adenosine receptors expressed in the cochlea. This study aims to extend our knowledge of purinergic signalling in the cochlea by comprehensively characterising the expression of the P2X4 receptor subtype. Wistar rat cochlea (embryonic day 20.5–6 weeks, both sexes) were collected, and the P2X4 expression was examined by immunohistochemistry. Robust P2X4 expression was found in the organ of Corti (OoC) in the inner hair cells (IHCs) and outer hair cells (OHCs), confirmed by double-labelling with hair cells (HCs) marker myosin VIIa. In IHCs, a robust cytoplasmic P2X4 expression occurred throughout the cell body, with the most intense signal at the medial side. In OHCs, P2X4 formed puncta near the apical and basal ends of the cell body. Using markers for subcellular organelles, P2X4 immunoreactivity was predominately associated with the trans-Golgi network apparatus and early endosomes in IHC and with early endosomes and lysosomes in OHC in the mature cochlea. In both cell types, some co-localisation of P2X4 with presynaptic marker was also observed. Taken together, these observations suggest unique roles for P2X4 in mature IHCs and OHCs as a purinergic receptor subtype responsible for the homeostatic regulation of hair cells and auditory sensory transduction.

Quantifying the effectiveness of superposed roughness elements to reduce dust emissions at the Salton Sea using computational fluid dynamics simulations - E. Furtak-Cole; J. A. Gillies; G. Nikolich; Y. Lin; S. Roy; J. Harrington (Air Quality, Atmosphere & Health, 2025)

Fluoride removal from groundwater via powder-nano MgO adsorption: novel adsorbents development and mechanisms studies novel adsorbents development and mechanisms studies - Jiun-Hau Ou; Ssu-Ching Chen; Wei-Zhe Lin; Francis Verpoort; Rao Y. Surampalli; Chih-Ming Kao (Environmental Science and Pollution Research, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Integrative analysis of coral plasticity and adaptations reveals key proteins driving resilience to changes in ocean carbonate chemistry - Xiangcheng Yuan; Ellias Y. Feng; Jingtian Wang; Lei Jiang; Tao Yuan; Hui Huang; Weihua Zhou; Jack Chi-Ho Ip; Wei-Jun Cai; Senjie Lin (Marine Life Science & Technology, 2025)
Understanding how corals adapt to changes in seawater carbonate chemistry is crucial for developing effective coral conservation strategies. Research to date has mostly focused on short-term experiments, overlooking long-term evolutionary effects. Here, we investigated the link between short-term stress responses and long-term genetic adaptations in the coral species Porites pukoensis through experiments under varying CO 2 and alkalinity conditions. Our results showed that alkalinity enrichment significantly increased coral calcification rates by 35%-45% compared to high CO 2 treatment, highlighting the potential of alkalinity enrichment to mitigate acidification impacts. Corals modulated relative expression levels of basic and acidic proteins in response to changes in seawater carbonate chemistry in the stress experiments. Genomic data revealed that this mechanism has been evolutionarily fixed in various organisms adapting to seawater carbonate chemistry. Additionally, both experimental and genomic results showed that extracellular matrix proteins, like collagen with von Willebrand factor type A domain, were modified in response to distinct carbonate environments. Molecular dynamics simulations and in-vitro experiments demonstrated that the structural stability of these proteins contributes to coral resilience under acidified conditions. This study established an integrated framework combining stress experiments, multi-omics analyses, molecular simulations, and in-vitro validation to identify key proteins involved in coral adaptation to acidification.

Single brand tire wear particles promote toxin-producing of an invasive cyanobacterium - Yuanyuan Mo; Jingxiang Lin; Xi Li; Hans-Peter Grossart; Lifeng Lin; Mekiso Y. Sido; Jun Yang (Environmental Research, 2025)

Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

A novel esterase MfdS catalyzes ester bond cleavage and promotes the degradation of mefenpyr-diethyl by Hansschlegelia zhihuaiae S113 - Houyu Yu; Rongrong Zhang; Lin Lai; JingJing Liang; Thamer Y. Mutter; Xing Huang (Journal of Environmental Chemical Engineering, 2025)

Histopathological and immunohistochemical characterisation of inflammatory lesions in flying foxes naturally infected with Australian Bat Lyssavirus (ABLV). - Y. Lin Tan; M. Gimeno; P. Pinczowski; S. Gestier; E. Hall; M. Krockenberger (Journal of Comparative Pathology, 2025)

In Vitro and Animal Studies of Human Natural Killer Cell-Derived Exosomes for the Treatment of Otitis Media - Zirui Zhao; Liqin Wang; Zhen Guo; Kanglun Jiang; Jianghong Xu; Yilai Shu; Christina Y. Xu; Jianning Zhang; Yunfeng Wang; Geng-Lin Li (Neuroscience Bulletin, 2025)

Non-extractant recycling of Ti, Fe, Ca and Al as value-added anatase, hematite, gypsum and nordstrandite from waste red mud - T. Su; S. Li; R. Bian; Y. Lin; S. Zhu (International Journal of Environmental Science and Technology, 2025)

Chlorination-properties-performance of polyamide nanofiltration membranes for the rejection of emerging contaminants - Wenhao Su; Wenyu Liu; Haowen Wu; Muhammad Saboor Siddique; Ying Mei; Yujing Qiu; Lin Lin; Hao Guo; Chuyang Y. Tang (Water Research, 2025)

P22-09 Toxicological Profiling of ZnO Nanoparticles: A Genotoxicity Mechanistic Study Using Alternative Test Methods - R.J. Chen; O. Lautan; S.-N. Chen; T.-Y. Lin; R. Pranata (Toxicology Letters, 2025)

Atmospheric transport of microplastics from land to sea is inefficient: Evidence from multimedia observations - Xiangrong Xu; Zhen Yuan; Yanxu Zhang; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Eddy Y. Zeng (Journal of Hazardous Materials, 2025)

Variation in uptake of sodium glucose cotransporter 2 inhibitors and glucagon-like peptide-1 receptor analogues in adults with type 2 diabetes at high cardiovascular risk - Juliana de Oliveira Costa; Jialing Lin; Tamara Y. Milder; Alys Havard; Jerry R. Greenfield; Richard O. Day; Brendon L. Neuen; Alice A. Gibson; Jedidiah I. Morton; Julian W. Sacre; Sallie-Anne Pearson; Michael O. Falster (European Journal of Clinical Pharmacology, 2025)
Purpose We quantified variation in the uptake of sodium-glucose co-transporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor analogues (GLP-1RA) across sociodemographic, behavioural and clinical characteristics of people with type 2 diabetes (T2D) at high cardiovascular risk. Methods We used the 45 and Up Study survey data (2018–2020) linked to dispensing and service claims for 10,171 people with T2D (56% male, median age of 72 years, median diabetes duration of 11 years). We calculated the prevalence of GLP-1RA and SGLT2i use within 1 year and used logistic regressions to assess associations with each participant characteristic. Results We found that 2270 (22.3%) people with T2D used SGLT2i and 679 (6.7%) used GLP-1RA. Use of these medicines was higher in people diagnosed with diabetes for a longer period, a high number of comorbidities and survey year, decreased in older people, and varied by sex. After adjusting for these factors, utilisation of these medicines was lower among people who consume alcohol (versus non-drinkers) and higher among those with overweight or obesity. SGLT2i use was also higher in people who were less physically active or had established cardiovascular disease and lower in people with anxiety or depression. GLP-1RA use was higher among people with poorer health and lower in people born outside Australia/New Zealand. Conclusion Prevalent use of SGLT2i and GLP-1RA was suboptimal and varied across clinical characteristics and behavioural risk factors. While some variation reflects complexities in prescribing for this older population, there remains opportunity for optimised prescribing within this high-risk population.

Lianas exhibit stronger conspecific negative density dependence than trees on tropical seedling survival - Zhenhua Sun; Nujaree Prachanun; Arunkamon Sonsuthi; Anuttara Nathalang; Wirong Chanthorn; Warren Y. Brockelman; Rong Gu; Nathan G. Swenson; Luxiang Lin (Ecology, 2025)
Conspecific negative density dependence (CNDD) strongly influences plant demography, especially in highly diverse tropical forests, but its relative importance may vary between growth forms. We used hierarchical Bayesian models to assess how neighbor densities affected the survival of more than 30,000 seedlings from 87 tree and 56 liana species in a tropical forest across two 1‐year census intervals. Although standardized CNDD coefficients were similar between lianas and trees, lianas showed a four‐ to sixfold stronger per capita CNDD on seedling survival compared to trees. Specifically, adding a single conspecific neighbor (2 cm dbh at 1 m distance) reduced liana survival by −1.2% to −1.8%, whereas it only reduced tree survival by 0.3%. Nevertheless, trees exhibited greater inter‐annual variation in CNDD prevalence (47%–11% of species with significant CNDD) compared to lianas (13%–23%). These contrasting patterns likely reflect growth form‐specific ecological strategies in density‐dependent responses to inter‐annual environmental fluctuations. Our findings highlight the importance of examining per capita neighborhood effects when assessing CNDD strength and suggest that lianas and trees may utilize different mechanisms driving CNDD and exhibit varying stability in their contribution to diversity maintenance in tropical forests.

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Driving factors of summer diurnal surface thermal environment in subtropical coastal cities: a Shenzhen case study - Q. Guo; Y. Lin; S. Zhong; X. Zhang (International Journal of Environmental Science and Technology, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Effect of fetch on street canyon flow field and pollutant dispersion - Daniel Ziyue Peng; Bingchao Zhang; Yunfei Fu; Xisheng Lin; Wenke Li; Tim K.T. Tse; Cruz Y. Li (Building and Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The system design of high-throughput miniature software-defined radio as a Ka/K-band communication payload for CubeSats - Kuan Po Chiu; Cissi Ying-tsen Lin; Yih-Min Chen; Jui-Hong Chou; Chi-Kuang Chao; Tiger J.-Y. Liu (Advances in Space Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Exogenous mitochondria added on benefits for cellular prion protein overexpression in adipose-derived mesenchymal stem cells treatment on intracranial hemorrhage rat - Kun-Chen Lin; Jui-Ning Yeh; Pei‐Hsun Sung; Tsung-Cheng Yin; John Y. Chiang; Chi-Ruei Huang; Yi-Ling Chen; Yi-Ting Wang; Kuan-Hung Chen; Hon‐Kan Yip (Journal of Molecular Histology, 2025)

A long-period assessment of climate change impact on river water quality in the central region of Iran - M. Moazeni; M. Sayedipour; K. Y. A. Lin; A. Ebrahimi (International Journal of Environmental Science and Technology, 2025)

Landsat 8 OLI atmospheric correction neural network for inland waters in tropical regions - M. Van Nguyen; O. T. La; H. T. T. Nguyen; D. Heriza; B.-Y. Lin; G. Y. I. Ryadi; Chao-Hung Lin; Vinh Quang Pham (International Journal of Environmental Science and Technology, 2025)

Analysis of Increased False-Positive ELISA Results for HIV in the Blood of Donors Infected with SARS-CoV-2 - H. Lin; Z. Wang; Q. Ren; Z. Cai; F. Ge; W. Yuan; T. Liao; Y. Wu; R. Peng; Y. Gu; Y. Kuang (Bulletin of Experimental Biology and Medicine, 2025)

An artificial intelligence and blockchain technology-based data management framework for multicenter randomized controlled trials - Dongyuan Yun; Xiaohang Wu; Xi Chen; Yahan Yang; Yuanjun Shang; Shaopeng Liu; Dinesh Visva Gunasekeran; Duoru Lin; Lixue Liu; Lanqin Zhao; Wenben Chen; Jingjing Chen; et al. (Science Bulletin, 2025)

Downregulation of A20 Expression Related to T Cells by Staphylococcal Enterotoxin A Treatment - X. Chen; Y. Yan; C. Lin; J. Yang; H. Qiu (Bulletin of Experimental Biology and Medicine, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Additional benefits of combined ceftriaxone and adipose-derived mesenchymal stem cells on revamping the outcomes in rodent after acute spinal infection - Tsung-Cheng Yin; Hung-Sheng Lin; Pei-Hsun Sung; John Y. Chiang; Chien-Hui Yang; Hon-Kan Yip; Kuan-Hung Chen (Journal of Molecular Histology, 2025)

Associations Between Lead and Cadmium Exposure and Subclinical Cardiovascular Disease in U.S. Adults - Lin Liu; Aimin Xu; Bernard M. Y. Cheung (Cardiovascular Toxicology, 2025)
The impact of lead and cadmium exposure on subclinical cardiovascular disease (CVD), indicated by elevated high-sensitivity cardiac troponin (hs-cTnT) and N-terminal pro b-type natriuretic peptide (NT-proBNP) remains uncertain. We analyzed data from participants aged 20 and older, without overt CVD, in the National Health and Nutrition Examination Survey (NHANES; 1999–2004). Elevated lead and cadmium levels were defined as 3.5 μg/dL and 1.0 μg/L (inductively coupled plasma mass spectrometry) and 3.8 μg/dL and 0.9 μg/L (atomic absorption spectrometry), respectively. Elevated hs-cTnT was ≥ 19 ng/L, and elevated NT-proBNP was ≥ 125 pg/mL. Multivariate logistic regression estimated the odds ratios (OR) and 95% confidence intervals (CI) for elevated biomarkers. Among 10,197 participants (mean age 48.8 years; 50.3% female), 5.3% had elevated hs-cTnT and 19.4% had elevated NT-proBNP. Elevated blood lead was associated with increased ORs for elevated hs-cTnT (OR 1.45, 95% CI 1.15–1.84) and NT-proBNP (OR 1.66, 95% CI 1.40–1.97). The corresponding ORs (95% CI) for elevated blood cadmium were 1.33 (1.02, 1.74) and 1.39 (1.18, 1.65). The effect of elevated blood lead on NT-proBNP was particularly pronounced among non-Hispanic Blacks (OR [95% CI], 3.26 [2.24, 4.74]) compared to Mexican Americans (1.46 [0.99, 2.17]) and non-Hispanic Whites (1.31 [1.02, 1.68]) and was stronger in individuals with impaired kidney function (OR [95% CI], 2.31 [1.43, 3.75]) compared to those with normal kidney function (1.44 [1.18, 1.75]). This study first reveals the association between lead and cadmium exposure and subclinical CVD, underscoring the need for targeted preventive measures to reduce cardiovascular risk and improve health outcomes.

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Efficient activation of UV-driven ozonation using ultrasonics for LDPE decomposition - A. Pattanateeradetch; C. Sakulthaew; Y.-T. Lin; A. Watcharenwong; A. Žgajnar Gotvajn; Y.-C. Chen; Q. Xu; C. Chokejaroenrat (Journal of Water Process Engineering, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Recovery of terephthalic acid from alkali-decrement wastewater by zinc salt-based coagulation - H. Zhu; C. Guo; C. Xu; Y. He; M. Huang; G. Zhou; Y. Lin (International Journal of Environmental Science and Technology, 2025)

Observations on Deraniyagala's beaked whale ( Mesoplodon hotaula ) in the South China Sea based on the first confirmed live sightings - Mingming Liu; Wenzhi Lin; Binshuai Liu; Shenglan Chen; Mingli Lin; Lijun Dong; Hui Kang; Mingyue Ouyang; Zixin Yang; Xiaoyu Huang; Massimiliano Rosso; L. Todd Pusser; et al. (Marine Mammal Science, 2025)
Deraniyagala's beaked whale, Mesoplodon hotaula , was previously known from eight published strandings and no confirmed live sightings, making it one of the least‐known cetaceans. We conducted six cetacean survey cruises in the South China Sea between 2019 and 2023, and during 120 sea‐days we recorded 12 sightings of unidentified Mesoplodon . From biopsy samples and acoustic recordings, five sightings were subsequently confirmed as M. hotaula. Using photographs, we provide the first field descriptions and observations of this species. The calf/juvenile has a distinctive facial coloration and dorsal striping pattern that appear to be diagnostic among Indo‐Pacific Mesoplodon ; among adult males, the dark rostrum of M. hotaula and the distinctively white‐tipped beak of ginkgo‐toothed beaked whale, M. ginkgodens , distinguish these similar‐looking, partially sympatric species. Mean group size was small (3.0, n = 5), with a preference for deep (2,156 m, n = 5), warm (30.3°C, n = 3) water. We update the known distribution of this species, present evidence of fishery interactions, and document the first reported mixed‐species Mesoplodon group: a juvenile Blainville's beaked whale M. densirostris associated with four M. hotaula. These sightings identify the South China Sea as a potentially important area for this almost completely unknown species.

Human life expectancy and season of birth in Taiwan: A retrospective cohort study - Tsutomu Nishimura; Eiji Nakatani; Mei-Chen Lin; Hiroyuki Yamauchi; Masanori Fukushima; Chung Y. Hsu (The Science of Nature, 2024)
Prior research has indicated a correlation between the birth season and life expectancy; however, many of these studies did not sufficiently account for comorbidities. In this comprehensive investigation, we aimed to meticulously explore the association between the birth month and life expectancy, giving due consideration to comorbidities. We used a robust dataset derived from Taiwan’s National Health Insurance Research Database (2000–2013), which allowed us to conduct a thorough examination. We divided our participants into four groups based on their season of birth: spring, summer, autumn, and winter. Propensity score matching was used to ensure an equitable distribution of demographic and clinical characteristics across the groups. Propensity scores were computed using logistic regression. Our model incorporated a broad range of demographic factors and comorbidities, providing rigorous adjustment for potential confounders. Our findings revealed a significantly increased risk of all-cause mortality among individuals born in spring, even after stringent adjustment for demographic factors and comorbidities. People born in spring demonstrated a 1.05-fold increase in the risk of all-cause mortality, with a hazard ratio of 1.05 and a 95% confidence interval of 1.01–1.09. Our study provides compelling evidence that helps understand the potential long-term impacts of a person’s birth season, which acts as a proxy for pregnancy / early-life environmental exposure, on life expectancy. These findings underscore the crucial need for additional research to illuminate the underlying biological and environmental mechanisms linking the birth season and lifespan of a person. The elucidation of these links could guide the development of innovative health promotion and disease prevention strategies that are tailored to an individual’s birth season.

Vitamin C alleviates hyperglycemic stress in retinal pigment epithelial cells - Hamid Alahmari; Chia-Chun Liu; Elizabeth Rubin; Venice Y. Lin; Paul Rodriguez; Kun-Che Chang (Molecular Biology Reports, 2024)

Construction and Behavioral Comparison of Two Mouse Models of Cerebral Palsy - Y. Tang; Y. Li; S. Lin; W. Wei; H. Chen (Bulletin of Experimental Biology and Medicine, 2024)

Long-term impact of Hurricane Maria on point-of-use drinking water quality in Puerto Rico and associated potential adverse health effects - Yishan Lin; Guangyu Li; Maria Sevillano Rivera; Tao Jiang; Irmarie Cotto; Corey M.G. Carpenter; Stephanie L. Rich; Roger W. Giese; Damian E. Helbling; Ingrid Y. Padilla; Zaira Rosario-Pabón; Akram N. Alshawabkeh; et al. (Water Research, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Short term air pollution exposure during pregnancy and associations with maternal immune markers - C.S. Yount; K. Scheible; S.W. Thurston; X. Qiu; Y. Ge; P.K. Hopke; Y. Lin; R.K. Miller; S.K. Murphy; J. Brunner; E. Barrett; T.G. O'Connor; et al. (Environmental Research, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

Fluid inclusion characteristics and mechanisms of tin mineralisation in the Jialong tin polymetallic deposits, Jiuwandashan–Yuanbaoshan, northern Guangxi, China - C-L. Meng; L-A. Bai; Z-H. Yue; S-Y. Zhou; Y. Dai; Z-H. Feng; X-J. Liu; H. Zhang; L-Z. Lin (Australian Journal of Earth Sciences, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Crustal-mantle layering deposits in the Von Kármán crater, South Pole-Aitken basin - Zhi Zhong; Yuqi Qian; Chenglong Li; Alexander Y. Sun; Zhongxian Cai; Lei Lin; Xu Guo; Yanbin Kuang; Shiqi Wen; Long Xiao (Earth and Planetary Science Letters, 2024)

Examining the sensitivity of ozone to NOx and VOCs in the Salt Lake City urban region from spatiotemporal patterns observed using stationary and mobile observations collected from a light-rail public transit platform - Andres Gonzalez; Derek Mallia; John C. Lin; Logan Mitchell; Taylor Y. Wilmot; Nancy Daher; Mark Sghiatti; Colin Harkins (Atmospheric Environment, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

Toxicity and metabolism of deoxynivalenol and its reversal by Bacillus subtilis in broiler chickens - Y. Lin; S. Wang; X. Deng; N. Liu; J. Wang (Animal Feed Science and Technology, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

Associations between follicular fluid trace elements and ovarian response during in vitro fertilization - Rooshna Mohsin; Victor Y. Fujimoto; Aubrey L. Galusha; Patrick J. Parsons; Jenna R. Krall; Celeste D. Butts-Jackson; Evelyn Mok-Lin; Michael S. Bloom (Environmental Research, 2024)

Resource utilization of coal chemical waste salt by bipolar membrane electrodialysis with thermal pretreatment - Haoran Xin; Xindi Chen; Songwei Lin; Haiping Luo; Yingjie Cao; Chuyang Y. Tang; Guangli Liu (Desalination, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Determinants of microbiome composition: Insights from free‐ranging hybrid zebras ( Equus quagga × grevyi ) - Joel O. Abraham; Bing Lin; Audrey E. Miller; Lucas P. Henry; Margaret Y. Demmel; Rosemary Warungu; Margaret Mwangi; Patrick M. Lobura; Luisa F. Pallares; Julien F. Ayroles; Robert M. Pringle; Daniel I. Rubenstein (Molecular Ecology, 2024)
The composition of mammalian gut microbiomes is highly conserved within species, yet the mechanisms by which microbiome composition is transmitted and maintained within lineages of wild animals remain unclear. Mutually compatible hypotheses exist, including that microbiome fidelity results from inherited dietary habits, shared environmental exposure, morphophysiological filtering and/or maternal effects. Interspecific hybrids are a promising system in which to interrogate the determinants of microbiome composition because hybrids can decouple traits and processes that are otherwise co‐inherited in their parent species. We used a population of free‐living hybrid zebras ( Equus quagga × grevyi ) in Kenya to evaluate the roles of these four mechanisms in regulating microbiome composition. We analysed faecal DNA for both the trn L‐P6 and the 16S rRNA V4 region to characterize the diets and microbiomes of the hybrid zebra and of their parent species, plains zebra ( E. quagga ) and Grevy's zebra ( E. grevyi ). We found that both diet and microbiome composition clustered by species, and that hybrid diets and microbiomes were largely nested within those of the maternal species, plains zebra. Hybrid microbiomes were less variable than those of either parent species where they co‐occurred. Diet and microbiome composition were strongly correlated, although the strength of this correlation varied between species. These patterns are most consistent with the maternal‐effects hypothesis, somewhat consistent with the diet hypothesis, and largely inconsistent with the environmental‐sourcing and morphophysiological‐filtering hypotheses. Maternal transmittance likely operates in conjunction with inherited feeding habits to conserve microbiome composition within species.

Biocontrol of strawberry Botrytis gray mold and prolong the fruit shelf-life by fumigant Trichoderma spp. - Q. S. Fan; H. J. Lin; Y. J. Hu; J. Jin; H. H. Yan; R. Q. Zhang (Biotechnology Letters, 2024)

Transcriptome analysis reveals the inhibitory mechanism of phloretin on virulence expression of Staphylococcus aureus and its application in cooked chicken - Hong Li; Changzhu Li; Ce Shi; Manal Y. Sameeh; Fahad Al-Asmari; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Dynamic efficiency evaluation of electric power and environmental treatment efficiency in China - Y. Li; Y. Chiu; T.-Y. Lin; S.-M. Wang; T.-H. Chang (International Journal of Environmental Science and Technology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Population parameters and heterogeneity in survival rates of Indo-Pacific humpback dolphins in a heavily urbanized coastal region of southeast China: implications for conservation - Wenzhi Lin; Leszek Karczmarski; Stephen C. Y. Chan; Ruiqiang Zheng; Yuen-Wa Ho; Yaqian Mo (Frontiers in Marine Science, 2024)
The Pearl River Delta (PRD) region on the southeast coast of China is among the largest and most populated metropolitan regions of the world, subjecting the Indo-Pacific humpback dolphins ( Sousa chinensis ) inhabiting coastal waters of this region – apparently the largest population of this species – to intense anthropogenic pressure. In this 5-year study (2011-2015), we applied mark-recapture techniques to quantify population parameters of humpback dolphins in the main body of the extensive estuarine system of the Pearl River, the Lingding Bay (LB), the most urbanized and industrialized part of PRD. The super-population size was estimated at 928 individuals (95% CI=823-1046), which however over-represents the latest number of extant animals. Annual estimates fluctuated between 708 and 750 dolphins, and likely reflect most accurately the latest/current number of humpback dolphins in waters of LB. Both the overall and annual estimates generated by our study are considerably lower than previously published abundance estimates. Apparent survival rates were generally low, estimated at 0.943 (SE = 0.008, 95% CI = 0.929-0.958) and 0.815 (SE = 0.025, 95% CI = 0.766-0.866) for adults and juveniles, respectively. In conjunction with limited recruitment, they may have led to a substantial decline in population numbers over the past two decades. Notably, dolphins exhibited heterogeneous apparent survival rates across the complex anthropogenic seascape of LB. Adult individuals that use Hong Kong waters as their primary habitat exhibited 6.2% higher survival rates than those in other parts of LB. This difference tripled (19.2%) for juveniles, a likely expression of their susceptibility to environmental and/or anthropogenic stresses. We suggest that the difference in survival is largely due to heterogeneous anthropogenic stressors that vary spatially across the estuary, among which habitat loss, pollution, and declining prey resources appear to be the primary threats. Based on our latest findings, we call for a strategic conservation planning with the highest priority given to preserve the remaining key dolphin habitats in Hong Kong waters, and to quantify and mitigate the impacts of major stressor(s) in Guangdong (mainland China) waters. Given the encroachment of ever-more-intense human activities on the coastal habitats of humpback dolphins, understanding their demographic response and the underlying mechanisms of the population processes may prove instrumental in the formulation of a conservation management strategy that can secure their continuous survival.

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Climate-driven changes to the spatial–temporal pattern of endangered tree Toona ciliata Roem. in China - Chunping Xie; Meng Li; Lin Chen; C. Y. Jim (Theoretical and Applied Climatology, 2024)

Study on seismic behavior and collapse risk of super high-rise braced mega frame-core tube structural system - Wenchen Shan; Xuhong Zhou; Xuchuan Lin; Lianjin Bao; Y. Frank Chen (Soil Dynamics and Earthquake Engineering, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Biogeochemical behavior of selenium in soil-air-water environment and its effects on human health - Z. N. Xu; Z. Q. Lin; G. S. Zhao; Y. B. Guo (International Journal of Environmental Science and Technology, 2024)

Remediation of diesel-oil contaminated soils using an innovative nanobubble and electrolyzed catalytic system - Wei-Ting Chen; Justin Chun-Te Lin; Shih-Hsiung Chen; Francis Verpoort; Kun-Liang Hong; Rao Y. Surampalli; Chih-Ming Kao (Journal of Cleaner Production, 2023)

Investigation of the Artificial Saliva and Saline Droplet Size Measurement Accuracy for COVID-19 Infection Control - Thomas Y. Wu; Yi-Hung Liu; Fang-hsin Lin; Yue Liu; Junjie Liu; Jinsang Jung; Wesley Zongrong Yu; Qinde Liu; Richard Y. C. Shin; Tang Lin Teo (Aerosol Science and Engineering, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

Interplay Between Inflammatory-immune and Interleukin-17 Signalings Plays a Cardinal Role on Liver Ischemia-reperfusion Injury—Synergic Effect of IL-17Ab, Tacrolimus and ADMSCs on Rescuing the Liver Damage - Sheung-Fat Ko; Yi-Chen Li; Pei-Lin Shao; John Y. Chiang; Pei-Hsun Sung; Yi-Ling Chen; Hon-Kan Yip (Stem Cell Reviews and Reports, 2023)

The effect of polychlorinated biphenyls extracted from offshore sediments on the intestinal epithelium and microflora of zebrafish - M. Zhang; D-H Zhu; Q-L Song; M-M Chen; Y Hu; D-J Kang; Z-B Chen; H-Y Lin; F-H Nie; J-J Chen (International Journal of Environmental Science and Technology, 2023)

Nano-wrinkled polyamide membrane preparation via heterogeneous surface-regulated interfacial polymerization for enhanced desalination performance - Zhiwen Li; Yanchao Xu; Liguo Shen; Renjie Li; Yang Jiao; Hongjun Lin; Chuyang Y. Tang (Desalination, 2023)

Considerations for Designing and Implementing a Multi-institution Undergraduate Medical Education Experience - Steven King; Emma Y. Wu; Christine Lin; Matthew Labriola; Myles Nickolich (Journal of Cancer Education, 2023)

Characterization of fouled ultrafiltration membranes from a full-scale wastewater reclamation plant in iron and steel industry - P.-H. Lin; Y.-C. Su; C.-L. Chen; I.-Y. Tsao (International Journal of Environmental Science and Technology, 2023)

Robust ceramic-based graphene membrane for challenging water treatment with enhanced fouling and scaling resistance - Chunyi Sun; Bin Lin; Xiangyong Zheng; Yingchao Dong; Min Zhao; Chuyang Y. Tang (Water Research, 2023)

Mn-MOFs-derived Mn2O3 as an effective peroxymonosulfate activator for the degradation of organics in water - V. D. Thao; N. T. Dung; N. D. Duc; T. T. Trang; D. T. M. Thanh; N. T. Phuong; N. T. Thuy; K.-Y. A. Lin; N. N. Huy (International Journal of Environmental Science and Technology, 2023)

The impact of education level on residents’ carbon consumption in China - Y.-N. Lin; Y.-H. Chiu; T.-H. Chang; T.-Y. Lin; S.-Y. Chiu (International Journal of Environmental Science and Technology, 2023)

Repeated manure inputs to a forage production soil increase microbial biomass and diversity and select for lower abundance genera - Jordan M. Sayre; Daoyuan Wang; Jonathan Y. Lin; Rachel E. Danielson; Kate M. Scow; Jorge L. Mazza Rodrigues (Agriculture, Ecosystems & Environment, 2023)

A monitoring system for CO2-EOR and storage based on reactive transport simulation of CO2 migration in groundwater - L. Li; Y. Wu; Q. Lin; Q. Wen; S. Chong (International Journal of Environmental Science and Technology, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Relating critical and limiting fluxes to metastable and long-term stable fluxes in colloidal membrane filtration through collision-attachment theory - Junxia Liu; Wei Fu; Xuri Yu; Haiyan Yang; Dongsheng Zhao; Zhihong Wang; Lin Wang; Xianhui Li; Chuyang Y. Tang (Water Research, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Characteristics and correlation of soil low-molecular-weight organic acids and nutrients in four plantations in red soil area of south China - Y. M. Ren; Z. J. Hou; T. Su; Z. R. Lin; A. Q. Liu; L. P. Cai (International Journal of Environmental Science and Technology, 2023)

Differences in the occurrence of leg glands between the social parasite S. mutica (Brown, 1949) and other Strumigenys ants - C. Wang; F.-Y. Chung; C.-C. Lin; J. Billen (Insectes Sociaux, 2023)

Water agricultural management based on hydrology using machine learning techniques for feature extraction and classification - Yi-Chia Lin; Almuhannad Sulaiman Alorfi; Tawfiq Hasanin; Mahendran Arumugam; Roobaea Alroobaea; Majed Alsafyani; Wael Y. Alghamdi (Acta Geophysica, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

Responses of coastal sediment organic and inorganic carbon to habitat modification across a wide latitudinal range in southeastern China - Yan Hong; Linhai Zhang; Ping Yang; Chuan Tong; Yongxin Lin; Derrick Y. F. Lai; Hong Yang; Yalian Tian; Wanyi Zhu; Kam W. Tang (CATENA, 2023)

Insights into solid phase denitrification in wastewater tertiary treatment: the role of solid carbon source in carbon biodegradation and heterotrophic denitrification - Ziwei Chen; Qingyang Zuo; Caihong Liu; Lin Li; Katherine Y. Deliz Quiñones; Qiang He (Bioresource Technology, 2023)

Insufficient evidence to link human exposure to heavy metals with biomarkers of glioma - Meng-Yi Xie; Guang-Long Huang; Zhi-Ying Lin; Xiang-Fei Sun; Chen-Chou Wu; Ya-Wei Liu; Liang-Ying Liu; Eddy Y. Zeng (Journal of Hazardous Materials, 2023)

Experimental assessment on the size effects of square concrete-filled steel tubular columns under axial compression - Pan Gao; Xuhong Zhou; Jiepeng Liu; Xuchuan Lin; Xuanding Wang; Y. Frank Chen (Engineering Structures, 2023)

Evolvement of carbamazepine under solar irradiation in the presence of chlorine: Efficiency, influences, degradation pathways and ecotoxicity - Haixiang Jia; Xiaoyan Y. Ma; Yu Lin; Shengjiong Yang; Yali An; Yihan Chen; Xiaochang C. Wang (Chemical Engineering Journal, 2023)

Ammonium removal characteristics of Delftia tsuruhatensis SDU2 with potential application in ammonium‑rich wastewater treatment - L. F. Chen; L. X. Chen; D. Pan; Y. L. Ren; J. Zhang; B. Zhou; J. Q. Lin; J. Q. Lin (International Journal of Environmental Science and Technology, 2023)

Characterizing breast cancer incidence and trends among Asian American, Native Hawaiian, and non-Hispanic White women in Hawaiʻi, 1990-2014 - Ugonna Ihenacho; Meg A. McKinley; Annie Vu; Brenda Y. Hernandez; Lenora W. M. Loo; Scarlett Lin Gomez; Anna H. Wu; Iona Cheng (Cancer Causes & Control, 2023)

Pyrolysis and Gasification Characteristics of Galdieria sulphuraria Microalgae - Fateme Banihashemi; Amr F. M. Ibrahim; Shuguang Deng; Jerry Y. S. Lin (BioEnergy Research, 2023)

Comparison of controlled drugs and new psychoactive substances (NPS) regulations in East and Southeast Asia - Olivia A. Lin; Pei-Jiun Chuang; Y. Jane Tseng (Regulatory Toxicology and Pharmacology, 2023)

Phytochemical composition and antibacterial evaluation of Tabernaemontana ventricosa Hochst. ex A. DC. leaf, stem, and latex extracts - C.M. Naidoo; Y. Naidoo; Y.H. Dewir; M. Singh; J. Lin (South African Journal of Botany, 2023)

Glioma is associated with exposure to legacy and alternative per- and polyfluoroalkyl substances - Meng-Yi Xie; Xiang-Fei Sun; Chen-Chou Wu; Guang-Long Huang; Po Wang; Zhi-Ying Lin; Ya-Wei Liu; Liang-Ying Liu; Eddy Y. Zeng (Journal of Hazardous Materials, 2023)

Simultaneous detection of two herbicides in fruits and vegetables with nanoparticle-linked immunosorbent and lateral flow immunoassays - Eunice Y. Kwon; Xiaofan Ruan; Fei Yu; Yuehe Lin; Dan Du; Bernard J. Van Wie (Food Chemistry, 2023)

Experimental assessment on the size effects of circular concrete-filled steel tubular columns under axial compression - Jiepeng Liu; Pan Gao; Xuchuan Lin; Xuanding Wang; Xuhong Zhou; Y. Frank Chen (Engineering Structures, 2023)

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

BCL11B Upregulates the Expression of RelA in T Cells Stimulated with Staphylococcal Enterotoxin A - Y. Yan; S. Wang; C. Lin (Bulletin of Experimental Biology and Medicine, 2022)

A comprehensive review on water stable metal-organic frameworks for large-scale preparation and applications in water quality management based on surveys made since 2015 - R. Y. Li; Z. S. Wang; Z. Y. Yuan; Constance Van Horne; Viatcheslav Freger; M. Lin; R. K. Cai; J. P. Chen (Critical Reviews in Environmental Science and Technology, 2022)

Effects of wetland, tide, and season on benthic biofilms and related sediment properties in mangrove ecosystems - Lihua Yang; Qian Yang; Li Lin; Tiangang Luan; Qiong Yang; Pu Li; Nora F. Y. Tam (Frontiers in Marine Science, 2022)
Sediment biofilms, mainly composed of diatoms, bacteria, and related extracellular polymeric substances (EPS), play important roles in mangrove ecosystems. In order to better understand the microbial biodiversity in marine environment, this study aims to clarify the effects of wetland, season, and tide on benthic biofilms and related sediment properties based on in situ investigation in two mangrove wetlands (Futian and Qi’ao) in the Pearl River Estuary, South China. Owing to the tide current, the northeastern Futian is more influenced by seawater than the southwestern Qi’ao. As a consequence of the salinity-driven accumulation of nutrients in sediments, Futian is more eutrophic than Qi’ao. Compared to Qi’ao, the higher nutrimental condition in Futian conserves higher abundance of eutrophic indicators of Nitzschia and Cyclotella , which results in higher values of all pigments and bound polysaccharide with varied monosaccharide composition. Compared to the seaward site, the landward site has higher abundance of benthic (pennate) diatoms but lower abundance of planktonic (centric) diatoms due to the varied settling velocity by tidal disturbance. This varied diatom composition leads to higher levels of bound polysaccharide and more monosaccharides in the landward site than in the seaward site. Compared to late spring (March), early summer (May) appears to have similar diatom abundance but more EPS fractions (except bound protein) and monosaccharides due to the higher level of light intensity and temperature. The observed lower bacterial abundance in May than in March might be due to the higher predation pressure. The baseline data on biofilm compositions in mangrove ecosystems from this study can improve the understanding of microbial biodiversity in response to the tidal, temporal, and spatial changes.

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

p38 MAPK Is a Major Regulator of Amyloid Beta-Induced IL-6 Expression in Human Microglia - Houmin Lin; Steven Grant Dixon; Wei Hu; Eric D. Hamlett; Junfei Jin; Adviye Ergul; Gavin Y. Wang (Molecular Neurobiology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Altered glucose metabolism and its association with carbonic anhydrase 8 in Machado-Joseph Disease - Guan-Yu Lin; Chung-Yung Ma; Li-Chung Kuo; Benjamin Y. Hsieh; Hanbing Wang; Chin-San Liu; Mingli Hsieh (Metabolic Brain Disease, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Shoot organogenesis and somatic embryogenesis in leaf tissue of Pulsatilla tongkangensis Y.N. Lee & T.C. Lee - Xiao-mei Zhao; Yu-ji Lian; Ze-lin Jin; Xue-jie Zhang; Yan Y; Shou-jin Fan (Plant Biotechnology Reports, 2022)

Ocean acidification in the Western Pacific: Boron isotopic composition recorded in a tropical massive coral core from Lanyu Islet SE Taiwan - Chen-Feng You; P-Y. Lin; Kuo-Fang Huang; Chuan-Hsiung Chung; Zhifei Liu (Frontiers in Marine Science, 2022)
Boron (B) and B isotopic compositions (δ 11 B) in biogenic carbonates are useful proxies for pH reconstruction in the ocean. However, high-resolution archives are scarce due to associated sampling and analytical difficulty. In this study, a modern long-lived massive coral skeleton ( Porites lobata ) from Lanyu Islet off southeast Taiwan was drilled and used for high-resolution major/trace element analyses, including trace elements B and δ 11 B, as well as oxygen and carbon isotopes, to investigate the associated environmental changes during 1991–1997. To avoid complicated biological influence, the top-most tissue layer was excluded in this study. The coralline records show a clear temporal trend in metal/Ca-based sea surface temperatures (SSTs) on annual and monthly timescales. In particular, the Mg/Ca-SSTs, the most sensitive temperature proxy at the site, show a significant warming trend (+0.2°C year −1 ) during the study period. On the other hand, subtle changes in the annual δ 11 B record were identified, corresponding to ~0.2 pH unit, which is comparable with other coral records in the Pacific, e.g., the South China Sea (SCS), Guam Island, Flinders, and Arlington Reef, as well as the in-situ seawater pH measurement at Hawaii station. This corresponds to an acidification rate of ~0.25 pH unit 100 year −1 , similar to other coralline data, in-situ pH/pCO 2 measurement, or model predictions, and emphasizes the importance of ocean acidification due to anthropogenic activities. Combined with the Mg/Ca-SST, the intra-annual data show a clear seasonal cycle with higher pH in winter, consistent with the pCO 2 at the oceanic surface. These chemical and isotopic results in corals conclude that marine biogenic carbonates are informative for oceanic pH reconstruction and can provide new insights into the relationships between climate changes and environmental responses on the coast of Taiwan.

Effects of pre-oxidation by ozone, permanganate and ferrate on generation and toxicities of disinfection byproducts - Y. Lin; Y. Lou; A. Li; Y. Wei; H. Li; M. Zhou; Y. Li (International Journal of Environmental Science and Technology, 2022)

Historical trend of probable maximum precipitation in Utah and associated weather types - Hongping Gu; S.‐Y. Simon Wang; Yen‐Heng Lin; Jonathan Meyer; Robert Gillies; Everett Taylor; Binod Pokharel (International Journal of Climatology, 2022)
This study assesses the impact global climate change has had on the theoretical upper limit of precipitation for Utah's watersheds by examining historical trends in probable maximum precipitation (PMP), a metric widely used for dam construction and management. Trends in the factors of PMP driven by both frontal and monsoonal storm scenarios were studied using two networks of surface weather stations and modern gridded datasets spanning 1981–2018. It was found that the historical trend in both 3‐hr and 24‐hr PMP estimations exhibited a statistically significant increasing trend, despite that the magnitude of the trend was sensitive to which dataset was examined and the data's spatial resolution. Over the 24‐hr time scale, an interesting deviation in PMP trends was found where frontal storm events demonstrated increasing PMP trends compared to decreasing PMP trends for monsoonal storm events. However, both storm types demonstrated increasing trends over shorter 3‐hr durations, suggesting a universal increase in convective storm intensity. PMP estimates also demonstrated a dependency on the type and resolution of meteorological data used, where higher‐resolution data generally produced greater PMP values and weaker trends. A discussion on the potential causes of these dependencies is provided. This study implies the need to take the historical PMP trend into account for future PMP estimates, especially when coarse‐resolution data are used for conventional PMP studies.

Genome skimming resolves the giant clam (Bivalvia: Cardiidae: Tridacninae) tree of life - Edwin Y. W. Tan; Z. B. Randolph Quek; Mei Lin Neo; Cécile Fauvelot; Danwei Huang (Coral Reefs, 2022)

Angiopoietin-Like Protein 4 Is Involved in Manganese Superoxide Dismutase-Mediated Suppression of Breast Cancer Cell Growth - P. Li; X. Zeng; Y. Liu; M. Lin (Bulletin of Experimental Biology and Medicine, 2022)

Bone tissue engineering using 3D silk scaffolds and human dental pulp stromal cells epigenetic reprogrammed with the selective histone deacetylase inhibitor MI192 - Kenny Man; Habib Joukhdar; Xue D. Manz; Mathieu Y. Brunet; Lin-Hua Jiang; Jelena Rnjak-Kovacina; Xuebin B. Yang (Cell and Tissue Research, 2022)
Epigenetics plays a critical role in regulating mesenchymal stem cells’ (MSCs) fate for tissue repair and regeneration. There is increasing evidence that the inhibition of histone deacetylase (HDAC) isoform 3 can enhance MSC osteogenesis. This study investigated the potential of using a selective HDAC2 and 3 inhibitor, MI192, to promote human dental pulp stromal cells (hDPSCs) bone-like tissue formation in vitro and in vivo within porous Bombyx Mori silk scaffolds. Both 2 and 5 wt% silk scaffolds were fabricated and characterised. The 5 wt% scaffolds possess thicker internal lamellae, reduced scaffold swelling and degradation rates, whilst increased compressive modulus in comparison to the 2 wt% silk scaffold. MI192 pre-treatment of hDPSCs on 5 wt% silk scaffold significantly enhanced hDPSCs alkaline phosphatase activity (ALP). The expression of osteoblast-related genes (RUNX2, ALP, Col1a, OCN) was significantly upregulated in the MI192 pre-treated cells. Histological analysis confirmed that the MI192 pre-treated hDPSCs-silk scaffold constructs promoted bone extracellular matrix (ALP, Col1a, OCN) deposition and mineralisation compared to the untreated group. Following 6 weeks of subcutaneous implantation in nude mice, the MI192 pre-treated hDPSCs-silk scaffold constructs enhanced the vascularisation and extracellular matrix mineralisation compared to untreated control. In conclusion, these findings demonstrate the potential of using epigenetic reprogramming and silk scaffolds to promote hDPSCs bone formation efficacy, which provides evidence for clinical translation of this technology for bone augmentation. Graphical abstract

Political ideology and psychological reactance: how serious should climate change be? - Eugene Y. Chan; Jack Lin (Climatic Change, 2022)

A bibliometric review of peripartum cardiomyopathy compared to other cardiomyopathies using artificial intelligence and machine learning - M. Grosser; H. Lin; M. Wu; Y. Zhang; S. Tipper; D. Venter; J. Lu; C. G. dos Remedios (Biophysical Reviews, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Petrological and isotopic data from Eocene granites in the Luocang area, South Lhasa terrane, Tibet: implications for the India–Eurasia collision - J.-G. Gao; F. Ding; J.-Q. Lin; Q.-H. Zhu; Y. Sun; X.-G. Xie (Australian Journal of Earth Sciences, 2021)

Differential DNA Methylation Profiles in Patients with Temporal Lobe Epilepsy and Hippocampal Sclerosis ILAE Type I - Wang Zhang; Haiyang Wang; Binchao Liu; Miaomiao Jiang; Yifei Gu; Shi Yan; Xian Han; Alicia Y. Hou; Chongyang Tang; Zhenfeng Jiang; Hong Shen; Meng Na; et al. (Journal of Molecular Neuroscience, 2021)

Individual Microcystis colonies harbour distinct bacterial communities that differ by Microcystis oligotype and with time - Derek J. Smith; James Y. Tan; McKenzie A. Powers; Xiaoxia N. Lin; Timothy W. Davis; Gregory J. Dick (Environmental Microbiology, 2021)

Optimization of methane production in a swine manure–rice straw anaerobic co-digestion process with sycamore sawdust biochar application - B. Jiang; Y. Lin; Y. Lun; Z. Xu (International Journal of Environmental Science and Technology, 2021)

Bringing resource management back into the environmental governance agenda: eco-state restructuring in China - Scott Y. Lin (Environment, Development and Sustainability, 2021)

Activation of Ca2+/Calmodulin-Dependent Protein Kinase II (CaMKII) with Lidocaine Provokes Pyroptosis of Glioblastoma Cells - B. Zhou; Y. Lin; S. Chen; J. Cai; Z. Luo; S. Yu; J. Lu (Bulletin of Experimental Biology and Medicine, 2021)

Pomelo fruit wastes are potentially valuable antioxidants, anti-inflammatories, antihypertensives, and antihyperglycemics - Li-Yun Lin; Chi-Yun Huang; Kuan-Chou Chen; Robert Y. Peng (Horticulture, Environment, and Biotechnology, 2021)
Grapefruit (G) parts contain abundant phenolic acids and flavonoids (PPNs and FLVs). The wastes created from exocarps, mesocarps (G wastes, GW) and waste blanching water (WBW) lead to a considerable loss of PPNs and FLVs. Here, we assessed Buntan (CB), Buntan Hayata (CBH), and Peiyu (CP) cultivars and observed considerable amounts of PPNs and FLVs. The ethanolic extracts of GW (GWE) and WBW contained gallic acid, protocatechuic acid, chlorogenic acid, caffeic acid, ferulic acid, coumaric acid, naringin, hesperidin, diosmin, quercetin, hesperetin, nobiletin, and tangeretin (GWC). GWE has previously been reported to be a relatively active antioxidant, anti-inflammatory (based on the expression of TNF-α in Raw264.7 cells), antihypertensive, and anti-hyperglycemic compound. The IC 50 values for antihyperglycemic activity with WBW for α-amylase were as follows: CB (27.96 ± 0.03 mg/mL) < CP (28.13 ± 0.19 mg/mL) < CBH (41.60 ± 0.16 mg/mL), and those for α-glucosidase were CB (1.80 ± 0.03 mg/mL) < CP (2.97 ± 0.29 mg/mL) < CBH (9.10 ± 0.51 mg/mL). GWC upregulated Glut4 in HepG2 cells, as well as the insulin secretion capability, and intracellular levels in RIN-m5F cells, and it downregulated DPP4 in HepG2 cells. The IC 50 values for the angiotensin-converting enzyme activity were: CBP (5.10 ± 0.02 mg/mL) < CB (7.24 ± 0.65 mg/mL) < CP (8.60 ± 2.03 mg/mL). Our results indicate that PPNs and FLVs present in GW are worth reclaiming.

Individual Microcystis colonies harbour distinct bacterial communities that differ by Microcystis oligotype and with time - Derek J. Smith; James Y. Tan; McKenzie A. Powers; Xiaoxia N. Lin; Timothy W. Davis; Gregory J. Dick (Environmental Microbiology, 2021)
Summary Interactions between bacteria and phytoplankton in the phycosphere have impacts at the scale of whole ecosystems, including the development of harmful algal blooms. The cyanobacterium Microcystis causes toxic blooms that threaten freshwater ecosystems and human health globally. Microcystis grows in colonies that harbour dense assemblages of other bacteria, yet the taxonomic composition of these phycosphere communities and the nature of their interactions with Microcystis are not well characterized. To identify the taxa and compositional variance within Microcystis phycosphere communities, we performed 16S rRNA V4 region amplicon sequencing on individual Microcystis colonies collected biweekly via high‐throughput droplet encapsulation during a western Lake Erie cyanobacterial bloom. The Microcystis phycosphere communities were distinct from microbial communities in whole water and bulk phytoplankton seston in western Lake Erie but lacked ‘core’ taxa found across all colonies. However, dissimilarity in phycosphere community composition correlated with sampling date and the Microcystis 16S rRNA oligotype. Several taxa in the phycosphere were specific to and conserved with Microcystis of a single oligotype or sampling date. Together, this suggests that physiological differences between Microcystis strains, temporal changes in strain phenotypes, and the composition of seeding communities may impact community composition of the Microcystis phycosphere.

Pomc Plays an Important Role in Sexual Size Dimorphism in Tilapia - Z. Y. Wan; V. C. L. Lin; Yue Gen Hua (Marine Biotechnology, 2021)

Clinacanthus nutans Mitigates Neuronal Death and Reduces Ischemic Brain Injury: Role of NF-κB-driven IL-1β Transcription - Mei-Han Kao; Jui-Sheng Wu; Wai-Mui Cheung; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Deron R. Herr; Teng-Nan Lin (NeuroMolecular Medicine, 2021)

Characterization and validation of QTLs for adult plant stripe rust resistance in Chinese wheat landrace Dabaimai - M. Y. Wang; M. R. Xu; F. T. Wang; S. J. A. Shah; J. Feng; R. M. Lin; S. C. Xu (Cereal Research Communications, 2021)

ManoMap: an automated system for characterization of colonic propagating contractions recorded by high-resolution manometry - Niranchan Paskaranandavadivel; Anthony Y. Lin; Leo K. Cheng; Ian Bissett; Andrew Lowe; John Arkwright; Saeed Mollaee; Phil G. Dinning; Gregory O’Grady (Medical & Biological Engineering & Computing, 2021)

Patterns of chronic disease management and health outcomes in a population-based cohort of Black women with breast cancer - Michelle Doose; Jennifer Tsui; Michael B. Steinberg; Cathleen Y. Xing; Yong Lin; Joel C. Cantor; Chi-Chen Hong; Kitaw Demissie; Elisa V. Bandera (Cancer Causes & Control, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

Approaching environmental human thermophysiological thresholds for the case of Ankara, Turkey - A. Santos Nouri; Y. Afacan; O. Çalışkan; Tzu-Ping Lin; A. Matzarakis (Theoretical and Applied Climatology, 2021)
The disclosed study undertook a ‘human centred-approach’ that ascertained and categorised environmental human thermophysiological risk factors by relating them to the human biometeorological system through the use of three widely utilised energy balance model (EBM) indices, the physiologically equivalent temperature (PET), the modified PET, and the universal thermal climate index (UTCI). The disclosed assessment was carried out over the past decade (i.e., 2010–2019) with a 3-h temporal resolution for the case of Ankara through two WMO meteorological stations to compare both local urban and peri-urban environmental conditions. The study recognised extreme annual variability of human physiological stress (PS) during the different seasons as a result of the biometeorological processing of the singular variables, which in the case of average PET for both stations, varied by up to 75 °C between the winter and summer for the same annual dataset (2012). In addition, all EBMs indicated higher heat stress within the city centre that were conducive of both urban extreme heatwaves and very hot days during the summer months, with extreme heat stress levels lasting for longer than a week with PET values reaching a maximum of 48 °C. Similar cold extremes were found for the winter months, with PET values reaching − 30 °C, and average PS levels varying lower in the case of the peri-urban station. Graphical abstract

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

Peripheral ProBDNF Delivered by an AAV Vector to the Muscle Triggers Depression-Like Behaviours in Mice - L. Y. Lin; S. Kelliny; L. C. Liu; M. Al-Hawwas; X. F. Zhou; L. Bobrovskaya (Neurotoxicity Research, 2020)

A lack of association between increases in gastrointestinal, liver, and urologic cancers and cyanobacterial contamination of fresh water lakes in Manitoba - Meaghan A. Labine; Emma Shu; Lin Xue; Giselle Mak; Jane Griffith; Gerald Y. Minuk (Environmental Science and Pollution Research, 2020)

Active ingredients of Inula helenium L. exhibits similar anti-cancer effects as isoalantolactone in pancreatic cancer cells - Y. Y. Yan; Q. Zhang; B. Zhang; B. Yang; N. M. Lin (Natural Product Research, 2020)

Testicular cancer in Hispanics: incidence of subtypes over time according to neighborhood sociodemographic factors in California - Mindy C. DeRouen; Meg McKinley; Sumit Anil Shah; Hala T. Borno; Rhonda Aoki; Daphne Y. Lichtensztajn; John T. Leppert; James D. Brooks; Benjamin I. Chung; Scarlett Lin Gomez; Iona Cheng (Cancer Causes & Control, 2020)

A Major Hydrothermal Reservoir Underneath the Tatun Volcano Group of Taiwan: Clues from a Dense Linear Geophone Array - C. H. Lin; Y. C. Lai; M. H. Shih; C. J. Lin; J. S. Ku; Y. C. Huang (Pure and Applied Geophysics, 2020)
A dense linear geophone array is deployed across the Tatun volcano group (TVG) at the northern tip of Taiwan, where more than 7 million residents live in the Taipei metropolis. The array is composed of 50 geophones with a station spacing of ~ 200 m in average, and it is designed for striking in the NW–SE direction to record the many earthquakes in eastern Taiwan, where the Philippine Sea plate subducted beneath the Eurasia plate. The detailed examination of felt earthquakes shows consistent P-wave delays are recorded at particular stations of the array. The further forward modeling indicates there is a low-velocity zone (LVZ) at depths between ~ 0.5 and ~ 2.5 km beneath the major fumarole sites. Combining this preliminary result with previous studies including clustering seismicity, volcanic earthquakes, low-resistivity zone, strong degassing processes and shallow velocity structures, we suggest that the LVZ might be associated with the major hydrothermal reservoir at the TVG. The identification of the hydrothermal reservoir by the LVZ not only implies a potential volcanic threat, such as phreatic eruptions, in the future, but also provides the possibility of sustainable geothermal resources for replacing traditional nuclear and fossil fuel power plants. Detailed images of the LVZ and other volcanic structures will be obtained soon when dense geophone arrays with more than 600 geophones are deployed from 2020 to 2022.

DNA methylation and histone acetylation changes to cytochrome P450 2E1 regulation in normal aging and impact on rates of drug metabolism in the liver - Mohamad M. Kronfol; Fay M. Jahr; Mikhail G. Dozmorov; Palak S. Phansalkar; Lin Y. Xie; Karolina A. Aberg; MaryPeace McRae; Elvin T. Price; Patricia W. Slattum; Philip M. Gerk; Joseph L. McClay (GeroScience, 2020)

Developing quantitative PCR assays to detect threatened and invasive freshwater turtles in Hong Kong using environmental DNA - Ivan P. Y. Lam; Yik-Hei Sung; Liu Lin; Jonathan J. Fong (Conservation Genetics Resources, 2020)

SLC9A4 in the organum vasculosum of the lamina terminalis is a [Na+] sensor for the control of water intake - Hiraki Sakuta; Chia-Hao Lin; Takeshi Y. Hiyama; Takashi Matsuda; Katsushi Yamaguchi; Shuji Shigenobu; Kenta Kobayashi; Masaharu Noda (Pflügers Archiv - European Journal of Physiology, 2020)

Assessment of ammonium fertilization as a stimulus for proline accumulation in Oryza sativa L. during cyanide assimilation - W. Liu; X.-Z. Yu; S.-Y. Lei; L. Yang; Y.-J. Lin (International Journal of Environmental Science and Technology, 2020)

Sedimentary environment and facies of the Huagang Formation in the northern central Xihu Depression, East China Sea Basin, China - Z. X. Zhao; C. M. Dong; C. Y. Lin; X. G. Zhang; X. Huang; B. J. Li; W. Guo; Z. Q. Zhu (Australian Journal of Earth Sciences, 2020)

A deep-level region-based visual representation architecture for detecting strawberry flowers in an outdoor field - P. Lin; W. S. Lee; Y. M. Chen; N. Peres; C. Fraisse (Precision Agriculture, 2020)

Managing water quality in a river basin with uncertainty - H.-W. Chen; W.-Y. Chen; C.-T. Wang; Y.-H. Lin; M.-J. Deng; C.-Y. Chiang (International Journal of Environmental Science and Technology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin - X. L. Sun; C. Y. Lin; X. G. Zhang; J. L. Lin; Z. X. Zhao; D. W. Huang; D. P. Duan (Australian Journal of Earth Sciences, 2019)

The Long-Term Effects of Ethanol and Corticosterone on the Mood-Related Behaviours and the Balance Between Mature BDNF and proBDNF in Mice - L. Y. Lin; S. Y. Luo; M. Al-Hawwas; M. F. Herselman; X. F. Zhou; Larisa Bobrovskaya (Journal of Molecular Neuroscience, 2019)

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Long-term Nutrient Fertilization Increased Soil Carbon Storage in California Grasslands - Yang Lin; Eric W. Slessarev; Scott T. Yehl; Carla M. D’Antonio; Jennifer Y. King (Ecosystems, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Cr-induced disturbance on expression of six COX genes in rice seedlings - X.-Z. Yu; C.-J. Lu; Y.-J. Lin; Y.-H. Li (International Journal of Environmental Science and Technology, 2019)

Climate of the weakly-forced yet high-impact convective storms throughout the Ohio River Valley and Mid-Atlantic United States - Binod Pokharel; S.-Y. Simon Wang; Jonathan Meyer; Robert Gillies; Yen-Heng Lin (Climate Dynamics, 2019)

Modulation of the southern Indian Ocean dipole on the impact of El Niño–Southern Oscillation on Australian summer rainfall - Hainan Gong; Wen Zhou; Wen Chen; Lin Wang; Marco Y.‐T. Leung; Paxson K.‐Y. Cheung; Yue Zhang (International Journal of Climatology, 2019)
This study investigates the modulation of the southern Indian Ocean dipole (SIOD) upon the impacts of the El Niño–Southern Oscillation (ENSO) on Australian summer rainfall (ASR) on an inter‐annual timescale. First the SIOD is identified as an important factor influencing rainfall anomalies over northeastern Australia via a zonal vertical circulation spanning from the southern Indian Ocean (SIO) to northern Australia. When ENSO and the SIOD are out of phase, the El Niño‐induced anticyclonic and convection anomalies shift eastwards to Australia and induce pronounced negative rainfall anomalies in northern Australia. When ENSO and the SIOD are in phase, the anticyclonic and convection anomalies extend westwards and generate an anomalous zonal vertical circulation, inducing positive rainfall anomalies in northeastern Australia. These different shifts in the circulation and rainfall anomalies with the two types of ENSO–SIOD occurrences are essentially attributed to the opposite effects of the different phases of SIOD events. The out‐of‐phase and in‐phase combinations of ENSO and the SIOD also largely form the dominant patterns of ASR variation. The significant influence of the SIOD on ASR indicates that the phase of the SIOD should be taken into account in the prediction of austral summer climate over Australia.

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

First observations of Tridacna noae (Röding, 1798) (Bivalvia: Heterodonta: Cardiidae) in Christmas Island (Indian Ocean) - Mei Lin Neo; Jeffrey K. Y. Low (Marine Biodiversity, 2018)

Carbon steel slag and stainless steel slag for removal of arsenic from stimulant and real groundwater - W. Shi; H. Li; G. Liao; G. Pei; Y. Lin (International Journal of Environmental Science and Technology, 2018)

Enhancement of photocatalytic activity of titanium dioxide using non-metal doping methods under visible light: a review - M. Nasirian; Y. P. Lin; C. F. Bustillo-Lecompte; M. Mehrvar (International Journal of Environmental Science and Technology, 2018)

Resistance to neomycin ototoxicity in the extreme basal (hook) region of the mouse cochlea - Shelly C. Y. Lin; Peter R. Thorne; Gary D. Housley; Srdjan M. Vlajkovic (Histochemistry and Cell Biology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Clinacanthus nutans Mitigates Neuronal Apoptosis and Ischemic Brain Damage Through Augmenting the C/EBPβ-Driven PPAR-γ Transcription - Jui-Sheng Wu; Mei-Han Kao; Hsin-Da Tsai; Wai-Mui Cheung; Jin-Jer Chen; Wei-Yi Ong; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Comparison of endosperm amyloplast development and degradation in waxy and non-waxy wheat - H. Yu; Y. Yang; X.Y. Chen; G.X. Lin; J.Y. Sheng; J.Y. Nie; Q.J. Wang; E.J. Zhang; X.R. Yu; Z. Wang; F. Xiong (Cereal Research Communications, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China - Zaipeng Yu; Minhuang Wang; Zhiqun Huang; Teng‐Chiu Lin; Matthew A. Vadeboncoeur; Eric B. Searle; Han Y. H. Chen (Global Change Biology, 2018)
Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2,736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO 2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations.

Dual Effect of Histidine on Polysorbate 20 Stability: Mechanistic Studies - Lin Zhang; Sandeep Yadav; Y. John Wang; Olivier Mozziconacci; Christian Schӧneich (Pharmaceutical Research, 2018)

Simulated differences in 21st century aridity due to different scenarios of greenhouse gases and aerosols - L. Lin; A. Gettelman; Q. Fu; Y. Xu (Climatic Change, 2018)

Spike densities of the amygdala and neocortex reflect progression of kindled motor seizures - Yu-Lin Wang; Sheng-Fu Liang; Alvin W. Y. Su; Fu-Zen Shaw (Medical & Biological Engineering & Computing, 2018)

IGF1R+ Dental Pulp Stem Cells Enhanced Neuroplasticity in Hypoxia-Ischemia Model - Hsiao-Yu Chiu; Chen-Huan Lin; Chung Y. Hsu; John Yu; Chia-Hung Hsieh; Woei-Cherng Shyu (Molecular Neurobiology, 2017)

Molecular screening of multidrug-resistance tuberculosis by a designated public health laboratory in Taiwan - H.-C. Lin; C.-L. Perng; Y.-W. Lai; F.-G. Lin; C.-J. Chiang; H.-A. Lin; R. Jou; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Approaches for Establishing Clinically Relevant Dissolution Specifications for Immediate Release Solid Oral Dosage Forms - Andre Hermans; Andreas M. Abend; Filippos Kesisoglou; Talia Flanagan; Michael J. Cohen; Dorys A. Diaz; Y. Mao; Limin Zhang; Gregory K. Webster; Yiqing Lin; David A. Hahn; Carrie A. Coutant; et al. (The AAPS Journal, 2017)

Effects of Ganoderma Lucidum shell-broken spore on oxidative stress of the rabbit urinary bladder using an in vivo model of ischemia/reperfusion - Robert M. Levin; Li Xia; Wu Wei; Catherine Schuler; Robert E. Leggett; Alpha D.-Y. Lin (Molecular and Cellular Biochemistry, 2017)

The Quantitative Structural and Compositional Analyses of Degenerating Intervertebral Discs Using Magnetic Resonance Imaging and Contrast-Enhanced Micro-Computed Tomography - Kevin H. Lin; Simon Y. Tang (Annals of Biomedical Engineering, 2017)

Helicobacter pylori infection increases the risk of adult-onset asthma: a nationwide cohort study - Y-C Wang; T-Y Lin; S-T Shang; H-J Chen; C-H Kao; C-C Wu; T-Y Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Risk factors and outcome of levofloxacin-resistant Elizabethkingia meningoseptica bacteraemia in adult patients in Taiwan - Y.-C. Huang; Y.-W. Huang; Y.-T. Lin; F.-D. Wang; Y.-J. Chan; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Experimental Investigation of the Anisotropic Mechanical Properties of a Columnar Jointed Rock Mass: Observations from Laboratory-Based Physical Modelling - H. Ji; J. C. Zhang; W. Y. Xu; R. B. Wang; H. L. Wang; L. Yan; Z. N. Lin (Rock Mechanics and Rock Engineering, 2017)

Gonorrhea infection increases the risk of prostate cancer in Asian population: a nationwide population-based cohort study - Y.-C. Wang; C.-H. Chung; J.-H. Chen; M.-H. Chiang; Ti-Yin; C.-H. Tsao; F.-H. Lin; W.-C. Chien; S.-T. Shang; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Increased risk of chronic osteomyelitis after hip replacement: a retrospective population-based cohort study in an Asian population - D.-Z. Hung; N. Tien; C.-L. Lin; Y.-R. Lee; C. C. N. Wang; J.-J. Chen; Y.-P. Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of dietary canthaxanthin on growth and body colour of blood parrot cichlid Amphilophus citrinellus × Paraneetroplus synspilus - M. Li; M. M. Rahman; B. Wu; Y.-C. Lin (Aquaculture International, 2017)

Variability of hydrological extreme events in East Asia and their dynamical control: a comparison between observations and two high-resolution global climate models - N. Freychet; A. Duchez; C.-H. Wu; C.-A. Chen; H.-H. Hsu; J. Hirschi; A. Forryan; B. Sinha; A. L. New; T. Graham; M. B. Andrews; C.-Y. Tu; et al. (Climate Dynamics, 2017)

Structuraland antigenic analysis of a new Rhoptry Pseudokinase Gene (ROP54) in Toxoplasma gondii - Jian Zhou; Gang Lu; Lin Wang; Aihua H. Zhou; Yali L. Han; Jingjing J. Guo; Pengxia X. Song; Huaiyu Y. Zhou; Hua Cong; Ming Hou; Shenyi Y. He (Acta Parasitologica, 2017)
is defined as an obligate intracellular apicomplexan parasite and influences approximatelyone-third of the human all over the world. ROP54 protein is expressed in the rhoptry of

Degradation Mechanisms of Polysorbate 20 Differentiated by 18O-labeling and Mass Spectrometry - Lin Zhang; Sandeep Yadav; Barthélemy Demeule; Y. John Wang; Olivier Mozziconacci; Christian Schӧneich (Pharmaceutical Research, 2017)

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

A new region-based preparatory factor for landslide susceptibility models: the total flux - C. C. Liu; W. Luo; M. C. Chen; Y. T. Lin; H. L. Wen (Landslides, 2016)

The agranular and granular insula differentially contribute to gambling-like behavior on a rat slot machine task: effects of inactivation and local infusion of a dopamine D4 agonist on reward expectancy - P. J. Cocker; M. Y. Lin; M. M. Barrus; B. Le Foll; C. A. Winstanley (Psychopharmacology, 2016)

Nutraceuticals in Neurodegeneration and Aging - Wei-Yi Ong; Grace Y. Sun; W. Gibson Wood; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Extracts Modulate Epigenetic Link to Cytosolic Phospholipase A2 Expression in SH-SY5Y Cells and Primary Cortical Neurons - Charlene Siew-Hon Tan; Christabel Fung-Yih Ho; Swan-Ser Heng; Jui-Sheng Wu; Benny Kwong-Huat Tan; Yee-Kong Ng; Grace Y. Sun; Teng-Nan Lin; Wei-Yi Ong (NeuroMolecular Medicine, 2016)

Clinacanthus nutans Protects Cortical Neurons Against Hypoxia-Induced Toxicity by Downregulating HDAC1/6 - Hsin-Da Tsai; Jui-Sheng Wu; Mei-Han Kao; Jin-Jer Chen; Grace Y. Sun; Wei-Yi Ong; Teng-Nan Lin (NeuroMolecular Medicine, 2016)

Infanticide in the Indo-Pacific humpback dolphin (Sousa chinensis) - Ruiqiang Zheng; Leszek Karczmarski; Wenzhi Lin; Stephen C. Y. Chan; Wei-Lun Chang; Yuping Wu (Journal of Ethology, 2016)

Changes in Sulforaphane and Selenocysteine Methyltransferase Transcript Levels in Broccoli Treated with Sodium Selenite - K. Huang; J. C. Lin; Q. Y. Wu; J. Y. Yan; M. Y. Liu; S. Zhang; W. J. Xiao (Plant Molecular Biology Reporter, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

PPAR-γ Ameliorates Neuronal Apoptosis and Ischemic Brain Injury via Suppressing NF-κB-Driven p22phox Transcription - Jui-Sheng Wu; Hsin-Da Tsai; Wai-Mui Cheung; Chung Y. Hsu; Teng-Nan Lin (Molecular Neurobiology, 2016)

Multiplexed Fluid Flow Device to Study Cellular Response to Tunable Shear Stress Gradients - Maggie A. Ostrowski; Eva Y. Huang; Vinay N. Surya; Charlotte Poplawski; Joseph M. Barakat; Gigi L. Lin; Gerald G. Fuller; Alexander R. Dunn (Annals of Biomedical Engineering, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A novel pathogenic bacteria ( Vibrio fortis ) causing enteritis in cultured seahorses, Hippocampus erectus Perry, 1810 - X Wang; Y Zhang; G Qin; W Luo; Q Lin (Journal of Fish Diseases, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Taxonomic Study of the Genus Apalacris Walker (Orthoptera: Catantopidae) - Z M Zheng; L L Lin; Y Niu (Neotropical Entomology, 2016)

Diesel degradation in soil catalyzed by the addition of a bioagent - Y. Lin; J.-J. Lay; W. K. Shieh (International Journal of Environmental Science and Technology, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

The impact of global budgeting on health service utilization, health care expenditures, and quality of care among patients with pneumonia in Taiwan - C.-Y. Lin; T. Ma; C.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Dopaminergic genetic variation moderates the effect of nicotine on cigarette reward - Paul T. Harrell; Hui-Yi Lin; Jong Y. Park; Melissa D. Blank; David J. Drobes; David E. Evans (Psychopharmacology, 2016)

Histological analysis of somatic embryogenesis in pineapple: AcSERK1 and its expression validation under stress conditions - J. Ma; Y. H. He; Z. Y. Hu; S. Kanakala; W. T. Xu; J. X. Xia; C. H. Guo; S. Q. Lin; C. J. Chen; C. H. Wu; J. L. Zhang (Journal of Plant Biochemistry and Biotechnology, 2016)

Biodegradation of atrazine by Arthrobacter sp. C3, isolated from the herbicide-contaminated corn field - H. Wang; Y. Liu; J. Li; M. Lin; X. Hu (International Journal of Environmental Science and Technology, 2016)

Effects of UV photodegradation on subsequent microbial decomposition of Bromus diandrus litter - Yang Lin; Rachel D. Scarlett; Jennifer Y. King (Plant and Soil, 2015)

Melatonin Ameliorates Arsenite-Induced Neurotoxicity: Involvement of Autophagy and Mitochondria - Y. C. Teng; Y. I. Tai; H. J. Huang; A. M. Y. Lin (Molecular Neurobiology, 2015)

Rapid generation and analysis of expressed sequence tags to uncovering inflorescence secondary metabolism of Bougainvillea spectabilis ‘Speciosas’ by pyrosequencing - S. X. Xu; Q. Y. Huang; C. S. Lin; F. C. Lin; L. X. Lin; Q. Y. Shen (Euphytica, 2015)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

The influence of shelf-sea fronts on winter monsoon over East China Sea - L.-Y. Oey; M.-C. Chang; S.-M. Huang; Y.-C. Lin; M.-A. Lee (Climate Dynamics, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Identification of a novel cyprinid herpesvirus 3 genotype detected in koi from the East Asian and South‐East Asian Regions - J Chen; D Chee; Y Wang; G Y Lim; S M Chong; Y N Lin; T Huangfu (Journal of Fish Diseases, 2015)
Cyprinid herpesvirus 3 (Cy HV ‐3) is a highly contagious virus that causes significant morbidity and mortality in common carp Cyprinus carpio L. and considered to be one of the most important pathogens of koi and common carp worldwide. Cyprinid herpesvirus 3 infected consignments imported from East Asian and South‐East Asian regions were identified during quarantine period in Singapore, and virus from a 2005 consignment was successfully isolated in koi fin cells. A combination of sequence analyses and duplex PCR were used to characterize 15 Cy HV ‐3 isolates detected in koi consignments between 2005 and 2011. Sequence analyses of the enlarged 9/5, SphI‐5 and TK gene regions identified both the Asian 1 ( n = 11) and European 4 ( n = 4) genotypes. Duplex PCR analysis of two variable marker regions between ORF 29 and ORF 30 (marker I) as well as ORF 133 and its upstream region (marker II ) revealed viruses of genotypes J (I ++ II + ), U/I (I −− II − ), an intermediate genotype (I ++ II − ) and a novel genotype, I ++ II +Δ , which was identified in viruses from seven different consignments. This novel genotype has a 13‐bp deletion in marker II , while maintaining the I ++ allele of marker I. The I ++ II +Δ genotype may have emerged from East Asian and South‐East Asian regions in recent years.

Crustal thickening and extension induced by the Great Sumatra–Andaman earthquake of 26 December 2004: revealed by the seismic moment tensor element Mrr - J.-Y. Lin; C.-L. Lo; W.-N. Wu; J.-C. Sibuet; S.-K. Hsu; Y.-Y. Wen (Marine Geophysical Research, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Neonatal urinary tract infection may increase the risk of childhood asthma - C.-H. Lin; Y.-C. Wang; W.-C. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Home paint exposures and risk of childhood acute lymphoblastic leukemia: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Catherine Metayer; Elizabeth Milne; Eleni Th. Petridou; Claire Infante-Rivard; Logan G. Spector; Jacqueline Clavel; John D. Dockerty; Luoping Zhang; Bruce K. Armstrong; Jérémie Rudant; Lin Fritschi; et al. (Cancer Causes & Control, 2015)

Molecular phylogeny and the underestimated species diversity of the endemic white‐bellied rat (Rodentia: Muridae: Niviventer ) in Southeast Asia and China - Liang Lu; Deyan Ge; Douglas Chesters; Simon Y. W. Ho; Ying Ma; Guichang Li; Zhixin Wen; Yongjie Wu; Jun Wang; Lin Xia; Jingli Liu; Tianyu Guo; et al. (Zoologica Scripta, 2015)
The white‐bellied rat, Niviventer , is a genus endemic to Southeast Asia and China. However, the interspecific phylogenetic relationships and species diversity of this genus remain poorly understood. In the present study, single and multi‐locus analyses were performed. Phylogenetic reconstruction on Cytochrome b (512 individuals, including data from Genbank) revealed five major clades with approximately 35 operational taxonomic units ( OTU s), a number twice the existing taxonomy. The first clade ( N . langbianis species group) was the earliest diverged. The second clade ( N. fulvescens species group) diverged in Southeast Asia, the south and lower altitude regions of the Hengduan Mountains, and Southeast China. The third clade (the N. eha species group) is endemic to high altitudes in Northwest Yunnan and the central region of Himalaya. The fourth clade (the N. andersoni species group), is mainly confined to alpine regions of the Hengduan Mountains. The fifth clade ( N . confucianus species group) is mainly distributed in the north and higher altitude regions of eastern Himalaya, the Hengduan Mountains and Taiwan, with the complex also invading central and northern China. Results from the combined dataset of four genes (Cytochrome b, Cytochrome oxidase subunit I, the D‐loop sequence of the mitochondrial genome and the first exon of the nuclear interphotoreceptor retinoid binding protein) for 82 representative individuals from China generally coincide with the result of the single gene, with 12 OTU s identified. These results provide a preliminary framework for the existing classification of this highly diversified genus. The divergence time of Niviventer based on the four gene topology was dated to the late Miocene ~6.41 Ma. Significant differences were detected in the general body form changes among these units based on voucher specimens. Moreover, geometric morphometric analysis of the cranium shape of voucher specimens indicated significant differences among five major species groups. Shape divergence of the cranium among several OTU s within the N. confucinaus complex is also significant. Our results provide further evidence for rapid and highly underestimated diversification of Niviventer both in genetics and morphology.

The application of the cluster identification method for the detection of leakages in water distribution networks - H.-Y. Lin; B.-W. Lin; P.-H. Li; J.-J. Kao (International Journal of Environmental Science and Technology, 2015)

The juxtamembrane sequence of the Hepatitis C virus polymerase can affect RNA synthesis and inhibition by allosteric polymerase inhibitors - Y. Wen; X. Lin; B. Fan; C. T. Ranjith-Kumar; C. C. Kao (Virus Genes, 2015)

Statins can increase the risk of herpes zoster infection in Asia - H.-H. Chen; C.-L. Lin; C.-J. Yeh; S.-Y. Yeh; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Balanitis is a risk factor for herpes zoster - C.-Y. Hsu; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mass mortality associated with a viral‐induced anaemia in cage‐reared large yellow croaker, Larimichthys crocea (Richardson) - W J Xu; Z D Qin; H Shi; N Jiang; Y Zhou; X L Liu; J J Xie; G S Wang; W M Wang; M Asim; L B Zeng; L Lin (Journal of Fish Diseases, 2015)

Arsenic Accumulation in Panax notoginseng Monoculture and Intercropping with Pteris vittata - L. Y. Lin; X. L. Yan; X. Y. Liao; Y. X. Zhang; X. Ma (Water, Air, & Soil Pollution, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

Feasibility and Analysis of Bipolar Concentric Recording of Electrohysterogram with Flexible Active Electrode - Y. Ye-Lin; J. Alberola-Rubio; G. Prats-boluda; A. Perales; D. Desantes; Javier Garcia-Casado (Annals of Biomedical Engineering, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Establishment of a novel, eco-friendly transgenic pig model using porcine pancreatic amylase promoter-driven fungal cellulase transgenes - Y. S. Lin; C. C. Yang; C. C. Hsu; J. T. Hsu; S. C. Wu; C. J. Lin; W. T. K. Cheng (Transgenic Research, 2015)

ICE1 demethylation drives the range expansion of a plant invader through cold tolerance divergence - H. J. Xie; H. Li; D. Liu; W. M. Dai; J. Y. He; S. Lin; H. Duan; L. L. Liu; S. G. Chen; X. L. Song; B. E. Valverde; S. Qiang (Molecular Ecology, 2015)
Cold tolerance adaption is a crucial determinant for the establishment and expansion of invasive alien plants into new cold environments; however, its evolutionary mechanism is poorly understood. Crofton weed ( Ageratina adenophora ), a highly invasive alien plant, is continuously spreading across subtropical areas in China, north‐eastward from the first colonized south‐western tropical regions, through cold tolerance evolution. Close relations between the cold tolerance levels of 34 populations, represented by 147 accessions, and the latitude, extreme lowest temperature, coldest month average temperature, and invasion period have provided direct insight into its cold tolerance divergence. A comparative study of the CBF pathway, associated with the cold tolerance enhancement of cold‐susceptible CBF 1 ‐transgenic plant, among four geographically distinct crofton weed populations revealed that the CBF pathway plays a key role in the observed cold tolerance divergence. Four epialleles of the cold response regulator ICE 1 ranged from 66 to 50 methylated cytosines, representing a 4.4% to 3.3% methylation rate and significantly corresponding to the lowest to highest cold tolerance levels among these different populations. The significant negative relation between the transcription levels of the primary CBF pathway members, except for CBF 2 , and the methylation levels among the four populations firstly demonstrates that the demethylation‐upregulated transcription level of CBF pathway is responsible for this evolution. These facts, combined with the cold tolerance variation and methylation found among three native and two other introduced populations, indicate that the ICE 1‐ demethylated upregulation of cold tolerance may be the underlying evolutionary mechanism allowing crofton weed to expand northward in China.

Chelator-enhanced phytoextraction of copper and zinc by sunflower, Chinese cabbage, cattails and reeds - T. Y. Yeh; C. L. Lin; C. F. Lin; C. C. Chen (International Journal of Environmental Science and Technology, 2015)

Helicobacter pylori infection and the risk of acute coronary syndrome: a nationwide retrospective cohort study - C.-Y. Lai; T.-Y. Yang; C.-L. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

High seroprevalence of human herpesvirus type 8 in patients with hepatocellular carcinoma - C.-C. Su; K.-C. Tseng; M.-N. Lin; T.-C. Hsieh; T.-Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Transynaptic Changes Evident in Peripheral Axonal Function After Acute Cerebellar Infarct - William Huynh; Cindy S-Y. Lin; Arun V. Krishnan; Steve Vucic; Matthew C. Kiernan (The Cerebellum, 2014)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

The complex interplay among bacterial motility and virulence factors in different Escherichia coli infections - C. Y. Kao; W. H. Lin; C. C. Tseng; A. B. Wu; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Impact of anthropogenic activities on urban stream water quality: a case study in Guangzhou, China - Jin-Song Liu; Ling-Chuan Guo; Xian-Lin Luo; Fan-Rong Chen; Eddy Y. Zeng (Environmental Science and Pollution Research, 2014)

Oxidative stress of maize roots caused by a combination of both salt stress and manganese deprivation - H.Q. Zhao; L. Wang; J. Hong; X.Y. Zhao; X.H. Yu; L. Sheng; C.Z. Hang; Y. Zhao; A.A. Lin; W.H. Si; F.S. Hong (Cereal Research Communications, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effect of nano-hematite morphology on photocatalytic activity - Y. H. Chen; C. C. Lin (Physics and Chemistry of Minerals, 2014)

The first record, tagging and release of a neonatal whale shark Rhincodon typus in Taiwan - H. H. Hsu; C. Y. Lin; S. J. Joung (Journal of Fish Biology, 2014)
On 27 October 2013, a Rhincodon typus was apparently chased by a group of Caranx ignobilis into nearshore waters near Green Island (Ludao), east of Taiwan. A fisherman brought it back to port where it was kept in a small sea pen until release. The R. typus was 78 cm total length, and was tagged and released on 29 October 2013.

Comparison of interpolation methods for estimating spatial distribution of precipitation in Ontario, Canada - S. Wang; G. H. Huang; Q. G. Lin; Z. Li; H. Zhang; Y. R. Fan (International Journal of Climatology, 2014)
In this study, different interpolation techniques in a geographical information system ( GIS ) environment are analysed and compared for estimating the spatial distribution of precipitation in the province of Ontario, Canada. A high‐resolution regional climate modelling system [Providing Regional Climates for Impacts Studies ( PRECIS )] is used to simulate the present (1961–1990) and future (2071–2100) precipitation events for 12 meteorological stations over Ontario. The results verify that for the present case PRECIS simulates well the precipitation events when compared with observed data. The future precipitation events can be projected after the validation of PRECIS . Six interpolation methods are then used to generate spatial distribution of precipitation based on the projections of future precipitation of 12 meteorological stations; they include inverse distance weighting ( IDW ), global polynomial interpolation ( GPI ), local polynomial interpolation ( LPI ), radial basis functions ( RBF ), ordinary kriging ( OK ), and universal kriging ( UK ). Cross‐validation is applied to evaluate the accuracy of interpolation methods in terms of the root mean square error ( RMSE ). The results indicate that LPI is the optimal method with the least RMSE for interpolating the PRECIS precipitation. LPI is then used to analyse spatial variations of the average annual precipitation for the period of 2071–2100 over Ontario.

Modeling chromium(VI) reduction by Escherichia coli 33456 using ceramic pearl as a supporting medium - Y.-H. Lin (International Journal of Environmental Science and Technology, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

On the origin of water-soluble organic tracer compounds in fine aerosols in two cities: the case of Los Angeles and Barcelona - M. Alier; M. Dall Osto; Y.-H. Lin; J. D. Surratt; R. Tauler; J. O. Grimalt; B. L. van Drooge (Environmental Science and Pollution Research, 2014)

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Lin Fritschi; Catherine Metayer; Claire Infante-Rivard; Corrado Magnani; Eleni Petridou; Eve Roman; Logan G. Spector; Peter Kaatsch; Jacqueline Clavel; Elizabeth Milne; John D. Dockerty; et al. (Cancer Causes & Control, 2014)

Convergent transcription through microsatellite repeat tracts induces cell death - William Y. Lin; Yunfu Lin; John H. Wilson (Molecular Biology Reports, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Clinical and microbiological characteristics of Klebsiella pneumoniae from community-acquired recurrent urinary tract infections - W. H. Lin; C. Y. Kao; D. C. Yang; C. C. Tseng; A. B. Wu; C. H. Teng; M. C. Wang; J. J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study - S.-Y. Tsai; T.-Y. Yang; H.-J. Chen; C.-S. Chen; W.-M. Lin; W.-C. Shen; C.-N. Kuo; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluation of seedling resistance of rice germplasm resources to sheath blight (Rhizoctonia solani) - B. Chen; L.-W. Li; Y.-J. Lin; Z.-H. Wang; G.-D. Lu (Cereal Research Communications, 2014)

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis - F. Lai; C. S. Song; Z. G. Ren; C. L. Lin; Q. C. Xu; Y. Li; C. G. Piao; S. S. Yu; M. W. Guo; G. Z. Tian (Australasian Plant Pathology, 2014)

Sulfur sources of sedimentary “buckshot” pyrite in the Auriferous Conglomerates of the Mesoarchean Witwatersrand and Ventersdorp Supergroups, Kaapvaal Craton, South Africa - B. M. Guy; S. Ono; J. Gutzmer; Y. Lin; N. J. Beukes (Mineralium Deposita, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Characterization, tissue distribution and regulation of neuropeptideY in Schizothorax prenanti - R. Wei; C. Zhou; D. Yuan; T. Wang; F. Lin; H. Chen; H. Wu; Z. Xin; S. Yang; Y. Wang; D. Chen; J. Liu; et al. (Journal of Fish Biology, 2014)
In this study, the full‐length neuropeptide Y ( npy ) complementary (c) DNA was cloned in ya fish Schizothorax prenanti . npy cDNA was composed of 789 nucleotides with a 288 nucleotide open reading frame encoding a protein of 96 amino acids. The deduced amino acid sequences contained a 28 amino acids signal peptide followed by a 36 amino acids mature neuropeptide Y (NPY). The npy mRNA was expressed mainly in the brain and eye as detected by real‐time quantitative polymerase chain reaction RT‐PCR ( rt‐qPCR ). The S. prenanti NPY was detectable from blastulation to hatch, suggesting that npy might be involved in the late embryonic development of S. prenanti . An experiment was conducted to determine the expression profile of npy during feeding of a single meal and during long‐term fasting. The expression level of npy in fed fish was significantly decreased at 0·5, 1·5, 3 and 9 h post‐feeding (hpf) than in fasting fish. Fasting for 14 days induced an increase in npy messenger (m) RNA expression in the brain. Overall, the results suggest that NPY is a conserved peptide that might be involved in the regulation of feeding and other physiological function in S. prenanti .

Characterization of Schizothorax prenanti cgnrhII gene: fasting affects cgnrhII expression - T. Wang; D. Yuan; C. Zhou; F. Lin; H. Chen; H. Wu; R. Wei; Z. Xin; J. Liu; Y. Gao; D. Chen; S. Yang; et al. (Journal of Fish Biology, 2014)
In this study, the role of chicken gonadotropin‐releasing hormone II ( cgnrhII ) in feeding regulation was investigated in Schizothorax prenanti . First, the full‐length S. prenanti cgnrhII cDNA consisted of 693 bp with an open reading frame of 261 bp encoding a protein of 86 amino acids. Next, cgnrhII was widely expressed in the central and peripheral tissues. Last, there were significant changes in cgnrhII mRNA expression in the fasted group compared to the fed group in the S. prenanti hypothalamus during 24 h fasting ( P cgnrhII gene expression presented a significant decrease in the fasted group compared with the fed group ( P cgnrhII mRNA expression level between refed and fed group on day 9 ( P > 0·05). Thus, the results suggest that cGnRH II expression is influenced by fasting and the gene may be involved in feeding regulation in S. prenanti.

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

Evaluation of adsorption potential of bamboo biochar for metal-complex dye: equilibrium, kinetics and artificial neural network modeling - Y. Yang; X. Lin; B. Wei; Y. Zhao; J. Wang (International Journal of Environmental Science and Technology, 2014)

Association between polymorphisms in the csrRS two-component regulatory system and invasive group A streptococcal infection - J.-N. Lin; L.-L. Chang; C.-H. Lai; H.-H. Lin; Y.-H. Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Detection of human JCPyV and BKPyV in diffuse large B-cell lymphoma of the GI tract - C. E. Tseng; C. M. Yeh; C. Y. Fang; J. Shay; P. L. Chen; M. C. Lin; D. Chang; M. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A novel rhizobacterium Bk7 for biological control of brown sheath rot of rice caused by Pseudomonas fuscovaginae and its mode of action - Kaleem Ullah Kakar; Y.-P. Duan; Zarqa Nawaz; Guochang Sun; Abdlwareth A. Almoneafy; M. Auwal Hassan; Ahmed Elshakh; Bin Li; Guan-Lin Xie (European Journal of Plant Pathology, 2014)

Using the VIKOR method to evaluate the design of a water quality monitoring network in a watershed - C.-L. Chang; Y.-T. Lin (International Journal of Environmental Science and Technology, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Enhancement of Non-Invasive Recording of Electroenterogram by Means of a Flexible Array of Concentric Ring Electrodes - J. Garcia-Casado; V. Zena-Gimenez; G. Prats-Boluda; Y. Ye-Lin (Annals of Biomedical Engineering, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Effects of UV Exposure and Litter Position on Decomposition in a California Grassland - Yang Lin; Jennifer Y. King (Ecosystems, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

Motor Cortex Excitability in Acute Cerebellar Infarct - William Huynh; Arun V. Krishnan; Steve Vucic; Cindy S-Y. Lin; Matthew C. Kiernan (The Cerebellum, 2013)

Pharmaceutical residues in tidal surface sediments of three rivers in southeastern China at detectable and measurable levels - Yongshan S. Chen; Shen Yu; Youwei W. Hong; Qiaoying Y. Lin; Hongbo B. Li (Environmental Science and Pollution Research, 2013)

Haematopoietic necrosis of cultured Prussian carp, C arassius gibelio ( B loch), associated with C yprinid herpesvirus 2 - Y Z Luo; L Lin; Y Liu; Z X Wu; Z M Gu; L J Li; J F Yuan (Journal of Fish Diseases, 2013)

Photosynthesis of temperate E ucalyptus globulus trees outside their native range has limited adjustment to elevated CO 2 and climate warming - Kristine Y. Crous; Audrey G. Quentin; Yan‐Shih Lin; Belinda E. Medlyn; David G. Williams; Craig V. M. Barton; David S. Ellsworth (Global Change Biology, 2013)
E ucalyptus species are grown widely outside of their native ranges in plantations on all vegetated continents of the world. We predicted that such a plantation species would show high potential for acclimation of photosynthetic traits across a wide range of growth conditions, including elevated [ CO 2 ] and climate warming. To test this prediction, we planted temperate E ucalyptus globulus Labill. seedlings in climate‐controlled chambers in the field located >700 km closer to the equator than the nearest natural occurrence of this species. Trees were grown in a complete factorial combination of elevated CO 2 concentration ( eC ; ambient [ CO 2 ] +240 ppm) and air warming treatments ( eT ; ambient +3 °C) for 15 months until they reached ca. 10 m height. There was little acclimation of photosynthetic capacity to eC and hence the CO 2 ‐induced photosynthetic enhancement was large (ca. 50%) in this treatment during summer. The warming treatment significantly increased rates of both carboxylation capacity ( V cmax ) and electron transport ( J max ) (measured at a common temperature of 25 °C) during winter, but decreased them significantly by 20–30% in summer. The photosynthetic CO 2 compensation point in the absence of dark respiration ( Γ *) was relatively less sensitive to temperature in this temperate eucalypt species than for warm‐season tobacco. The temperature optima for photosynthesis and J max significantly changed by about 6 °C between winter and summer, but without further adjustment from early to late summer. These results suggest that there is an upper limit for the photosynthetic capacity of E . globulus ssp. globulus outside its native range to acclimate to growth temperatures above 25 °C. Limitations to temperature acclimation of photosynthesis in summer may be one factor that defines climate zones where E . globulus plantation productivity can be sustained under anticipated global environmental change.

Isolation and molecular analysis of genes Stpk-V2 and Stpk-V3 homologous to powdery mildew resistance gene Stpk-V in a Dasypyrum villosum accession and its derivatives - Z. S. Lin; Y. L. Zhang; M. J. Wang; J. R. Li; K. Wang; X. Chen; Q. F. Xu; X. S. Zhang; X. G. Ye (Journal of Applied Genetics, 2013)

Role of HO-1 in the Arsenite-Induced Neurotoxicity in Primary Cultured Cortical Neurons - Y. C. Teng; Y. I. Tai; Y. H. Lee; A. M. Y. Lin (Molecular Neurobiology, 2013)

Pushover analysis of reinforced concrete frames considering shear failure at beam-column joints - Y. C. Sung; T. K. Lin; C. C. Hsiao; M. C. Lai (Earthquake Engineering and Engineering Vibration, 2013)

Soluble interleukin‐1 receptor, a potential negative regulator of orange‐spotted grouper Epinephelus coioides interleukin‐1 system - D. Q. Lu; M. Yao; S. B. Yi; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2013)
In this study, the cDNA sequence encoding interleukin‐1 ( Il ‐1) receptor‐like protein of orange‐spotted grouper Epinephelus coioides was obtained. The newly identified sequence was named soluble type I Il ‐1 receptor ( sIl‐1rI ) owing to its structural composition, which had two Ig‐like domains, lack of transmembrane region and the Toll/interleukin‐1 receptor ( TIR ) domain, similar to the brown rat Rattus norvegicus soluble Il‐1rI . In addition, sequence comparison and phylogenetic analysis indicated that E. coioides sequence had a closer relationship with Il‐1rI than Il‐1rII . Real‐time PCR revealed that sil‐1rI mRNA expression presented a process of decrease, restoration and increase in Cryptocaryon irritans ‐infected E. coioides . The negative correlation between Il ‐1β and sil‐1rI mRNA in C. irritans ‐infected head‐kidney implied the potential negative regulatory role of sil‐1rI in E. coioides Il ‐1 system. The leucocytes incubated with lipopolysaccharide or polyriboinosinic polyribocytidylic acid exhibited different expression profiles of sil‐1rI . Recombinant Il ‐1β ( rIl ‐1β) protein was capable of inducing sil‐1rI mRNA under the concentration of 100 ng ml −1 , suggesting that high dosage or excess Il ‐1β would stimulate the expression of sil‐1rI to maintain the homoeostasis of E. coioides Il ‐1 system. For the first time, the role of teleost Il‐1rI in parasite infection has been identified, and soluble Il‐1r was found in fish.

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Structure–activity relationship study of growth inhibitory 2-styrylchromones against carcinoma cells - Chen Lin; Pei-Jung Lu; Chia-Ning Yang; Christopher Hulme; Arthur Y. Shaw (Medicinal Chemistry Research, 2013)

Effect of Zinc Source on Performance, Zinc Status, Immune Response, and Rumen Fermentation of Lactating Cows - Run L. Wang; Jian G. Liang; Lin Lu; Li Y. Zhang; Su F. Li; Xu G. Luo (Biological Trace Element Research, 2013)

High-resolution profiles of iron, manganese, cobalt, cadmium, copper and zinc in the pore water of estuarine sediment - Z. Yang; W. Guo; Y. Fan; C. Lin; M. He (International Journal of Environmental Science and Technology, 2013)

Neuroanatomical consequences of very preterm birth in middle childhood - Ilyse D. Lax; Emma G. Duerden; Sarah Y. Lin; M. Mallar Chakravarty; Elizabeth J. Donner; Jason P. Lerch; Margot J. Taylor (Brain Structure and Function, 2013)

Impact of mercury on denitrification and denitrifying microbial communities in nitrate enrichments of subsurface sediments - Yanping Wang; Heather A. Wiatrowski; Ria John; Chu-Ching Lin; Lily Y. Young; Lee J. Kerkhof; Nathan Yee; Tamar Barkay (Biodegradation, 2013)

A New Vector for Identification of Prokaryotes and Their Variable-Size Genomes - Tao Hou; Fu Liu; Caixia X. Lin; Dingyuan Y. Li (Current Microbiology, 2013)

Analysis of carbamazepine serum by differential pulse voltammetry (DPV) and comparison with fluorescence polarization immunoassay (FPIA): an animal study - W. Y. Lin; M. L. Pan; H. Y. Wang; Y. O. Su; P. W. Huang (Medicinal Chemistry Research, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

The expression of HIF-1α in primary hepatocellular carcinoma and its correlation with radiotherapy response and clinical outcome - Zuo-Lin Xiang; Zhao-Chong Zeng; Jia Fan; Zhao-You Tang; Jian He; Hai-Ying Zeng; Joe Y. Chang (Molecular Biology Reports, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

Biodegradation of Cypermethrin by a newly isolated actinomycetes HU-S-01 from wastewater sludge - Q. S. Lin; S. H. Chen; M. Y. Hu; M. R. Ul Haq; L. Yang; H. Li (International Journal of Environmental Science and Technology, 2011)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Migration of silver from nanosilver–polyethylene composite packaging into food simulants - H. Song; B. Li; Q.-B. Lin; H.-J. Wu; Y. Chen (Food Additives & Contaminants: Part A, 2011)

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics - Leslie C. Sheu; Patricia Zheng; Anabelle D. Coelho; Lisa D. Lin; Patricia S. O’Sullivan; Bridget C. O’Brien; Albert Y. Yu; Cindy J. Lai (Journal of Cancer Education, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Quantitative trait loci for temperature-sensitive resistance to Puccinia striiformis f. sp. tritici in wheat cultivar Flinor - J. Feng; L. L. Zuo; Z. Y. Zhang; R. M. Lin; Y. Y. Cao; S. C. Xu (Euphytica, 2011)

Seroprevalence of Mycoplasma hyopneumoniae in pigs in subtropical southern China - Y. He; M. J. Xu; D. H. Zhou; F. C. Zou; R. Q. Lin; C. C. Yin; X. H. He; R. Liang; M. Liang; X. Q. Zhu (Tropical Animal Health and Production, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Evaluation of potential integration of entrapped mixed microbial cell and membrane bioreactor processes for biological wastewater treatment/reuse - Jia Zhu; C. F. Lin; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2011)

Algal Growth Control Within Natural Water Purification Systems: Macrophyte Light Shading Effects - T. Y. Yeh; T. Y. Ke; Y. L. Lin (Water, Air, & Soil Pollution, 2011)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Groundwater Assessment at Manukan Island, Sabah: Multidisplinary Approaches - S. M. Praveena; C. Y. Lin; A. Z. Aris; M. H. Abdullah (Natural Resources Research, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Development of EST-PCR markers for Thinopyrum intermedium chromosome 2Ai#2 and their application in characterization of novel wheat-grass recombinants - M. J. Wang; Y. Zhang; Z. S. Lin; X. G. Ye; Y. P. Yuan; W. Ma; Z. Y. Xin (Theoretical and Applied Genetics, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Combined Method for Reduction of High Frequency Interferences in Surface Electroenterogram (EEnG) - Y. Ye-Lin; J. Garcia-Casado; G. Prats-Boluda; J. L. Martinez-de-Juan (Annals of Biomedical Engineering, 2010)

A Simple Allometric Diffusion-Based Biokinetic Model to Predict Cu(II) Uptake Across Gills of Freshwater Clam Corbicula fluminea - W.-Y. Chen; C.-M. Lin; Y.-R. Ju; C.-M. Liao (Bulletin of Environmental Contamination and Toxicology, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Occurrence of Aliphatic Hydrocarbons in Water, Suspended Particulate Matter and Sediments of Daliao River System, China - W. Guo; M. C. He; Z. F. Yang; C. Y. Lin; X. C. Quan (Bulletin of Environmental Contamination and Toxicology, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Effects of two species of inorganic arsenic on the nutrient physiology of rice seedlings - Hai Bin Wang; H. B. He; G. D. Yang; C. Y. Ye; B. H. Niu; W. X. Lin (Acta Physiologiae Plantarum, 2010)

Artificial neural network analysis for reliability prediction of regional runoff utilization - S. C. Lee; H. T. Lin; T. Y. Yang (Environmental Monitoring and Assessment, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Seroprevalence of Toxoplasma gondii infection in breeding sows in Western Fujian Province, China - C. Q. Huang; Y. Y. Lin; A. L. Dai; X. H. Li; X. Y. Yang; Z. G. Yuan; X. Q. Zhu (Tropical Animal Health and Production, 2010)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Genetic variation in colchicine-treated regenerated plants of Eucalyptus globulus Labill. - X. Z. Liu; H. Lin; X. Y. Mo; T. Long; H. Y. Zhang (Journal of Genetics, 2009)

Do otolith annular structures correspond to the first freshwater entry for yellow European eels Anguilla anguilla in the Baltic countries? - Y.‐J. Lin; J.‐C. Shiao; L. Ložys; M. Plikšs; A. Minde; Y. Iizuka; I. Rašals; W.‐N. Tzeng (Journal of Fish Biology, 2009)
To examine the relationship between freshwater entry and otolith annular structures, a total of 113 naturally recruited European eels Anguilla anguilla from Lithuania and Latvia that entered fresh water at least once were collected. In some individuals (8·3–11·3%), the first freshwater entry coincided with a dark check that was distinctly different from neighbouring annuli. In most individuals (81·7–84·9%), the first freshwater entry occurred on rings and increments indistinguishable from other annuli. For the remaining individuals (3·8–10%), the first freshwater entry did not correspond to any otolith ring, band or annulus. According to recent evidence, the observed high correspondence between the first freshwater entry and otolith annuli was more likely due to the movement into fresh water during winter when the annulus was deposited, rather than stress resulting from habitat change. Consequently, the age estimation based on otoliths might be less influenced by this habitat change during the yellow eel stage.

Transpositional activation of mPing in an asymmetric nuclear somatic cell hybrid of rice and Zizania latifolia was accompanied by massive element loss - X. H. Shan; X. F. Ou; Z. L. Liu; Y. Z. Dong; X. Y. Lin; X. W. Li; B. Liu (Theoretical and Applied Genetics, 2009)

Application of integrated GIS and multimedia modeling on NPS pollution evaluation - C. E. Lin; C. M. Kao; Y. C. Lai; W. L. Shan; C. Y. Wu (Environmental Monitoring and Assessment, 2009)

Molecular characterization of two potato virus S isolates from late-blight-resistant genotypes of potato (Solanum tuberosum) - Y. H. Lin; K. L. Druffel; J. Whitworth; M. J. Pavek; Hanu R. Pappu (Archives of Virology, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Spatio‐temporal variation in the elemental compositions of otoliths of southern bluefin tuna Thunnus maccoyii in the Indian Ocean and its ecological implication - C. H. Wang; Y. T. Lin; J. C. Shiao; C. F. You; W. N. Tzeng (Journal of Fish Biology, 2009)
The elements Na, Mg, Mn, Ca, Sr and Ba in otoliths of southern bluefin tuna Thunnus maccoyii , collected from their feeding ground in the central Indian Ocean and spawning ground between southern Java and north‐western Australia were measured by laser‐ablation inductively coupled plasma mass spectrometry (LA‐ICPMS) and compared among sampling locations and developmental stages. The Na, Mg and Mn to Ca concentration ratios were significantly higher at the larval stage than at the adult stage, and the ratio reached a peak at the first inflection point of the otolith, mean ± s.d. 43·3 ± 4·9 days after hatching and decreased sharply to a low level thereafter. The temporal change of the elements:Ca ratios in the first inflection point corresponded to the life stage transition from larva to juvenile, indicating that the uptake rate of elements from ambient waters was significantly influenced by the ontogenetic change in the fish. The elemental composition at the otolith edge differed significantly in sub‐adults on the feeding grounds and adults on the spawning grounds. Thus, the otolith elemental composition can be used as a biological tracer to study the time of the ontogenetic shift and to reconstruct the past migratory environmental history of T. maccoyii . In addition, the elemental composition of the otolith core of the adult was similar between feeding and spawning grounds, indicating that the fish in the Indian Ocean had the same larval origin, which is consistent with the single spawning population hypothesis.

A Two-Step Infinite α-Cuts Fuzzy Linear Programming Method in Determination of Optimal Allocation Strategies in Agricultural Irrigation Systems - H. W. Lu; G. H. Huang; Y. P. Lin; L. He (Water Resources Management, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Study on the Relationship Between Meteorological Conditions and Acid Rain in Mid-Eastern Fujian - C. C. Lin; J. X. Liu; Y. Y. Cai; B. L. Li; Z. L. Wang; B. B. Chen (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification of soil heavy metal sources from anthropogenic activities and pollution assessment of Fuyang County, China - X. Y. Zhang; F. F. Lin; Mike T. F. Wong; X. L. Feng; K. Wang (Environmental Monitoring and Assessment, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Modelling the growth of Japanese eel Anguilla japonica in the lower reach of the Kao‐Ping River, southern Taiwan: an information theory approach - Y. J. Lin; W. N. Tzeng (Journal of Fish Biology, 2009)
Information theory was applied to select the best model fitting total length ( L T )‐at‐age data and calculate the averaged model for Japanese eel Anguilla japonica compiled from published literature and the differences in growth between sexes were examined. Five candidate growth models were the von Bertalanffy, generalized von Bertalanffy, Gompertz, logistic and power models. The von Bertalanffy growth model with sex‐specific coefficients was best supported by the data and nearly overlapped the averaged growth model based on Akaike weights, indicating a similar fit to the data. The Gompertz, generalized von Bertalanffy and power growth models were also substantially supported by the data. The L T at age of A. japonica were larger in females than in males according to the averaged growth mode, suggesting a sexual dimorphism in growth. Model inferences based on information theory, which deal with uncertainty in model selection and robust parameter estimates, are recommended for modelling the growth of A. japonica .

EMMC technology for treatment/reuse of dilute dairy wastewater - Rhoda Luo-Ting Lin; Joshua Lelemia Irvine; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2009)

Prevalence of helminths in water buffaloes in Hunan Province, China - Y. Liu; F. Li; W. Liu; R. S. Dai; Y. M. Tan; D. S. He; R. Q. Lin; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Rotavirus infection increases the risk of bacteremia in children with nontyphoid Salmonella gastroenteritis - T.-Y. Hung; M.-C. Liu; C.-F. Hsu; Y.-C. Lin (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Hotelling Revisited: Oil Prices and Endogenous Technological Progress - C.-Y. Cynthia Lin; Haoying Meng; Tsz Yan Ngai; Valeria Oscherov; Yan Hong Zhu (Natural Resources Research, 2009)

Insights from a Simple Hotelling Model of the World Oil Market - C.-Y. Cynthia Lin (Natural Resources Research, 2009)

A quick and efficient approach for gene silencing by using triple putative microRNA-based short hairpin RNAs - Z. X. Shan; Q. X. Lin; M. Yang; C. Y. Deng; S. J. Kuang; Z. L. Zhou; D. Z. Xiao; X. Y. Liu; S. G. Lin; X. Y. Yu (Molecular and Cellular Biochemistry, 2009)

Raman spectroscopic study of K-lingunite at various pressures and temperatures - Lin-gun Liu; C.-C. Lin; Y. J. Yung; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Group A streptococcal infection caused by emm1 strains among children in southern Taiwan - H.-C. Lin; S.-M. Wang; Y.-L. Lin; Y.-S. Lin; J.-J. Wu; W.-J. Chuang; M. T. Lin; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Induction potential of clavulanic acid toward L1 and L2 β-lactamases of Stenotrophomonas maltophilia - C.-W. Lin; R.-M. Hu; S.-C. Huang; Y.-J. Hsiao; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Mapping chromosomal regions affecting flowering time in a spring wheat RIL population - F. Lin; S. L. Xue; D. G. Tian; C. J. Li; Y. Cao; Z. Z. Zhang; C. Q. Zhang; Z. Q. Ma (Euphytica, 2008)

Identification of wheat line YW243 on comprehensive resistance to several diseases by pathogens and molecular markers - H. Xie; Z. Lin; Z. Zhang; L. Du; Z. Xin; Y. Ma; X. Ye; X. Chen (Cereal Research Communications, 2008)

The development of extremely dry surface air due to vertical exchanges under the exit region of a jet streak - Michael L. Kaplan; C. Huang; Y.-L. Lin; J. J. Charney (Meteorology and Atmospheric Physics, 2008)

Extended Probability Perturbation Method for Calibrating Stochastic Reservoir Models - Lin Y. Hu (Mathematical Geosciences, 2008)

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

The influence of mesoscale mountains on vortex tracks: shallow-water modeling study - C.-Y. Huang; Y.-L. Lin (Meteorology and Atmospheric Physics, 2008)

Expression and significance of PTEN and VEGF in canine mammary gland tumours - C. W. Qiu; D. G. Lin; J. Q. Wang; C. Y. Li; G. Z. Deng (Veterinary Research Communications, 2008)

Note: Anti-viral activity ofAilanthus altissima crude extract onRice stripe virus in rice suspension cells - J. G. Yang; Y. G. Dang; G. Y. Li; L. J. Guo; W. T. Wang; Q. W. Tan; Q. Y. Lin; Z. J. Wu; L. H. Xie (Phytoparasitica, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Yersinia enterocolitica infection in diarrheal patients - H. Zheng; Y. Sun; S. Lin; Z. Mao; B. Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Assessment of sampling designs to measure riverine fluxes from the Pearl River Delta, China to the South China Sea - Hong-Gang Ni; Feng-Hui Lu; Xian-Lin Luo; Hui-Yu Tian; Ji-Zhong Wang; Yu-Feng Guan; She-Jun Chen; Xiao-Jun Luo; Eddy Y. Zeng (Environmental Monitoring and Assessment, 2008)

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Determination of Particulate-Bound Formaldehyde from Burning Incense by Solid Phase Microextraction - S. W. Liou; C. Y. Chen; T. T. Yang; J. M. Lin (Bulletin of Environmental Contamination and Toxicology, 2008)

Detection of quantitative trait loci controlling extremely early heading in rice - Y. Nonoue; K. Fujino; Y. Hirayama; U. Yamanouchi; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2008)

Multiple-Point Simulations Constrained by Continuous Auxiliary Data - Tatiana L. Chugunova; Lin Y. Hu (Mathematical Geosciences, 2008)

Using FANP approach on selection of competitive priorities based on cleaner production implementation: a case study in PCB manufacturer, Taiwan - M. L. Tseng; Y. H. Lin; A. S. F. Chiu; J. C. H. Liao (Clean Technologies and Environmental Policy, 2008)

Bioavailability Effect of Methylprednisolone by Polymeric Micelles - Ching-Lin Chen; Shwu-Fen Chang; Daniel Lee; Lang-Yo Yang; Yi-Hsuan Lee; Chung Y. Hsu; Shwu-Jiuan Lin; Jiahorng Liaw (Pharmaceutical Research, 2008)

Spatiotemporal dynamics of bacterial populations in the anoxic Cariaco Basin - Xueju Lin; Mary I. Scranton; Andrei Y. Chistoserdov; Ramon Varela; Gordon T. Taylor (Limnology and Oceanography, 2008)
Distributions of bacterial populations in the anoxic Cariaco Basin were studied over 2 yr (five cruises) at three stations using fluorescence in situ hybridization (FISH) and terminal restriction fragment length polymorphism (T‐RFLP) of 16S ribosomal ribonucleic acid (rRNA) genes. FISH results demonstrate that the contribution of ɛ‐proteobacterial abundances to total prokaryotic inventories was relatively constant among cruises, and this group was dominant in the redoxcline, accounting for 18% of DAPI (4'6‐diamidino‐2‐phenylindole)‐stained counts on average. In contrast, β‐proteobacteria were more variable. Sulfate reducers, α‐, and γ‐proteobacteria accounted for minor components of the anaerobic microbial communities. T‐RFLP fingerprinting also showed significant temporal shifts in bacterial community composition. The greatest variations in bacterial community structure were evident among oxic, transitional, and anoxic zones, but significant horizontal variations were also evident within redoxclines of three different stations. A statistical analysis of T‐RFLP patterns revealed clear spatiotemporal patterns in bacterial community structure along the redox gradient among sites and over time. Total prokaryotic abundances corresponded well with seasonal variations in organic carbon fluxes above the redoxcline. However, no single measured environmental variable (O 2 , H 2 S, S 2 O 3 2‐ , H 4 SiO 4 , NO 3 − , PO 4 3‐ , microbial biomass, chemoautotrophic production) explained the temporal oscillations of the dominant bacterial groups. Analyses suggest that redox gradients, terrestrial inputs, and disturbance due to lateral intrusions of adjacent waters could significantly affect bacterial community composition in the Cariaco Basin.

Growth differences between naturally recruited and stocked European eel Anguilla anguilla from different habitats in Lithuania - Y.‐J. Lin; L. Ložys; J.‐C. Shiao; Y. Iizuka; W.‐N. Tzeng (Journal of Fish Biology, 2007)
European eels Anguilla anguilla from freshwater lakes in Lithuania had slower growth rates and lower backcalculated total lengths ( L T ) than those from lagoons and coastal waters, but no significant differences were found among fish with different migratory histories or between naturally recruited and stocked fish except a higher L T at age of stocked European eels at ages 5 to 8 years. The asymptotic L T did not differ among habitats or migratory histories, but the stocked eels in the lakes had smaller K (coefficient from the von Bertalanffy growth function) than did the both naturally recruited and stocked eels in the lagoon and coastal waters. The growth rate of European eels in Lithuania might be influenced mainly by different habitats rather than different migratory histories and stocking. The lower L T at age of naturally recruited fish at ages 5–8 years compared to stocked fish might result from the extra energy costs entailed in migration from the Atlantic and across the Baltic Sea.

Experiences of water transfer from the agricultural to the non-agricultural sector in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan; Y. L. Sung (Paddy and Water Environment, 2007)

Salmonellae and Campylobacters in Household and Stray Dogs in Northern Taiwan - H.-J. Tsai; H.-C. Huang; C.-M. Lin; Y.-Y. Lien; C.-H. Chou (Veterinary Research Communications, 2007)

Fracture network characteristics of a deep borehole in the Table Mountain Group (TMG), South Africa - L. Lin; H. Jia; Y. Xu (Hydrogeology Journal, 2007)

Culture Duration Modulates Collagen Hydrolysate-Induced Tissue Remodeling in Chondrocyte-Seeded Agarose Hydrogels - Kenneth W. Ng; Justin D. Saliman; Evan Y. Lin; Lauren Y. Statman; Lindsay E. Kugler; Sean B. Lo; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Volatile Organic Compound Exposure of Suburban Elementary Students in Taiwan - C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2007)

Accumulation of additive effects generates a strong photoperiod sensitivity in the extremely late-heading rice cultivar ‘Nona Bokra’ - Y. Uga; Y. Nonoue; Z. W. Liang; H. X. Lin; S. Yamamoto; U. Yamanouchi; M. Yano (Theoretical and Applied Genetics, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Responses of Metapopulation Dynamics to Two Different Kinds of Habitat Destruction Caused by Human Activities - H. Y. Liu; Z. S. Lin; T. Wen (Plant Ecology, 2006)

Multifunctionality of paddy fields in Taiwan - C. C. Huang; M. H. Tsai; W. T. Lin; Y. F. Ho; C. H. Tan (Paddy and Water Environment, 2006)

Pharmacogenomics of Phenolic Antioxidant Butylated Hydroxyanisole (BHA) in the Small Intestine and Liver of Nrf2 Knockout and C57BL/6J Mice - Sujit Nair; Changjiang Xu; Guoxiang Shen; Vidya Hebbar; Avantika Gopalakrishnan; Rong Hu; Mohit Raja Jain; Wen Lin; Young-Sam Keum; Celine Liew; Jefferson Y. Chan; Ah-Ng Tony Kong (Pharmaceutical Research, 2006)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Novel polymorphic microsatellites for studying genetic diversity of red Asian arowanas - G. H. Yue; Z. Y. Zhu; G. Lin; L. C. Lo; F. Feng (Conservation Genetics, 2006)

Detection of Hong Kong 97-like H5N1 influenza viruses from eggs of Vietnamese waterfowl - Y. Li; Z. Lin; J. Shi; Q. Qi; G. Deng; Z. Li; X. Wang; G. Tian; H. Chen (Archives of Virology, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Climatic Change, Wars and Dynastic Cycles in China Over the Last Millennium - David D. Zhang; C. Y. Jim; George C-S Lin; Yuan-Qing He; James J. Wang; Harry F. Lee (Climatic Change, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Potential Volatile Organic Compound Exposure from Dry Process Photocopiers in Operation-Idle Mode - D.-J. Hsu; H.-L. Huang; H.-Y. Lin; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Ancient paddy soils from the Neolithic age in China’s Yangtze River Delta - Z. H. Cao; J. L. Ding; Z. Y. Hu; H. Knicker; I. Kögel-Knabner; L. Z. Yang; R. Yin; X. G. Lin; Y. H. Dong (The Science of Nature, 2006)

Renoprotective effects of combination of angiotensin converting enzyme inhibitor with mycophenolate mofetil in diabetic rats - Y. -G. Wu; H. Lin; H Qian; M. Zhao; X. -M. Qi; G. -Z. Wu; S. -T. Lin (Inflammation Research, 2006)

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Protoplast electrofusion between common wheat (Triticum aestivum L.) and Italian ryegrass (Lolium multiflorum Lam.) and regeneration of mature cybrids - T. M. Ge; X. H. Lin; F. L. Qin; S. W. Yu; Y. J. Yu (In Vitro Cellular & Developmental Biology - Plant, 2006)

Mapping QTL associated with resistance to Fusarium head blight in the Nanda2419 × Wangshuibai population. II: Type I resistance - F. Lin; S.L. Xue; Z.Z. Zhang; C.Q. Zhang; Z.X. Kong; G.Q. Yao; D.G. Tian; H.L. Zhu; C.J. Li; Y. Cao; J.B. Wei; Q.Y. Luo; et al. (Theoretical and Applied Genetics, 2006)

The Complete Mitochondrial Genome Sequence and Characterization of Single-Nucleotide Polymorphisms in the Control Region of the Asian Seabass (Lates calcarifer) - G. Lin; L. C. Lo; Z. Y. Zhu; F. Feng; R. Chou; G. H. Yue (Marine Biotechnology, 2006)

Nucleotide sequence and mRNA expression analysis of β-actin gene in the orange-spotted grouper Epinephelus coioides - W. M. Zhang; Y. Zhang; L. H. Zhang; S. G. Wang; T. Y. Zhu; D. Lin; G. Z. Ma (Fish Physiology and Biochemistry, 2005)

Comparison of (−)-Epigallocatechin-3-Gallate Elicited Liver and Small Intestine Gene Expression Profiles Between C57BL/6J Mice and C57BL/6J/Nrf2 (−/−) Mice - Guoxiang Shen; Changjiang Xu; Rong Hu; Mohit R. Jain; Sujit Nair; Wen Lin; Chung S. Yang; Jefferson Y. Chan; A.-N. Tony Kong (Pharmaceutical Research, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Isolation and characterization of actinomycetes antagonistic to pathogenic Vibrio spp. from nearshore marine sediments - J. L. You; L. X. Cao; G. F. Liu; S. N. Zhou; H. M. Tan; Y. C. Lin (World Journal of Microbiology and Biotechnology, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

Phylogenetic analysis of classical swine fever virus in Taiwan - C. H. Pan; M. H. Jong; T. S. Huang; H. F. Liu; S. Y. Lin; S. S. Lai (Archives of Virology, 2005)

Etoposide (VP-16) sensitizes p53-deficient human non-small cell lung cancer cells to caspase-7-mediated apoptosis - C.-C. Chiu; C.-H. M. Y. Lin; K. Fang (Apoptosis, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 1: A 44-case study synoptic observational analyses - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. J. Charney; A. J. Riordan; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Characterizing the severe turbulence environments associated with commercial aviation accidents. Part 2: Hydrostatic mesoscale numerical simulations of supergradient wind flow and streamwise ageostrophic frontogenesis - M. L. Kaplan; A. W. Huffman; K. M. Lux; J. D. Cetola; J. J. Charney; A. J. Riordan; Y.-L. Lin; K. T. Waight (Meteorology and Atmospheric Physics, 2005)

Formation and Emission of Chlorinated by-Products from a Bench-Scale Packed-Bed Odor Scrubber - Chi-Wen Lin; Daniel P. Y. Chang (Water, Air, & Soil Pollution, 2005)

Orographic effects on a conditionally unstable flow over an idealized three-dimensional mesoscale mountain - S.-H. Chen; Y.-L. Lin (Meteorology and Atmospheric Physics, 2005)

Evaluation of Genotoxicity of Combined Pollution by Cadmium and Atrazine - A. J. Lin; Y. G. Zhu; Y. P. Tong; C. N. Geng (Bulletin of Environmental Contamination and Toxicology, 2005)

Histology and histochemical enzyme‐staining patterns of major immune organs in Epinephelus malabaricus - H.‐T. Lin; H.‐Y. Lin; H.‐L. Yang (Journal of Fish Biology, 2005)
The histological architecture of major immune organs in the Malabar grouper Epinephelus malabaricus was investigated. The novel characteristics such as melanomacrophage centres (MMCs) appeared in the thymus and lymphopoietic tissue formed as foci in the head kidney. Leukocyte distribution in organs was identified by enzyme histochemistry. β‐glucuronidase (BG) reactive cells in the cortex region of the thymus were botryoidally aggregated. Both acid phosphatase (AcP) and BG reactive cells concentrated within the specialized lymphopoietic foci in the head kidney, suggesting that the foci might be functional. Primitive histological characters of immunity were observed in the spleen. Although leukocyte aggregation was demonstrated in the spleen, additional enzyme histochemistry indicated that the aggregate might not be the equivalent of white pulp found in other vertebrates. The histological evidence did not support intestinal involvement in the immune system: there was no demonstrable gut associated lymphoid tissue. The limited distribution in the cortex and medulla boundary and the condensed format of the lymphocytes suggests a functional role for the MMC in the thymus of E. malabaricus . The MMC appearance in the thymus of a teleost was unusual.

Manganese Uptake and Accumulation by Two Populations of Phytolacca acinosa Roxb. (Phytolaccaceae) - S. G. Xue; Y. X. CHEN; A. J. M. Baker; R. D. Reeves; X. H. Xu; Q. Lin (Water, Air, & Soil Pollution, 2005)

Optimising the tissue culture conditions for high efficiency transformation of indica rice - Y. J. Lin; Qifa Zhang (Plant Cell Reports, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

Fisheries of two tropical lagoons in Ghana, West Africa - H. R. Dankwa; J. M. Shenker; J. Lin; P. K. Ofori‐Danson; Y. Ntiamoa‐Baidu (Fisheries Management and Ecology, 2004)
The fisheries of two coastal lagoons, Keta and Songor, were studied as part of Ghana Coastal Wetlands Management Project (GCWMP) aimed at sustainable exploitation of wetland resources. Fish samples were obtained with seine nets and cast net as well as from local fishermen. Water quality parameters (pH, dissolved oxygen, temperature and turbidity) were similar in the two lagoons, except for salinity, which was significantly different ( P Sarotherodon melanotheron Rüppell, and the redchin tilapia, Tilapia guineensis (Bleeker), being the most important commercial fishes in both lagoons. The number of individuals for each species in Songor Lagoon were far more abundant, with densities several orders of magnitude higher than in Keta Lagoon. However, both species were significantly larger ( P S. melanotheron and T. guineensis respectively. Over‐fishing, use of small‐size mesh nets, limited mixing of marine and fresh water were some of the factors limiting fish production in both lagoons.

Identification of a 98-kb DNA segment containing the rice Eui gene controlling uppermost internode elongation, and construction of a TAC transgene sublibrary - Y.-H. Xu; Y.-Y. Zhu; H.-C. Zhou; Q. Li; Z.-X. Sun; Y.-G. Liu; H.-X. Lin; Z.-H. He (Molecular Genetics and Genomics, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Natural frequency assessment of stability of root keeper magnetic devices - H. -M. Huang; D. -Z. Liu; Y. -Y. Shiau; C. -Y. Yeh; C. -T. Lin; S. -Y. Lee (Medical & Biological Engineering & Computing, 2004)

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

Predicted ATP-binding cassette systems in the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; H. Wang; R. W. Hammond; R. Jomantiene; Q. Liu; S. Lin; B. A. Roe; R. E. Davis (Molecular Genetics and Genomics, 2004)

Kinetic Studies on the Effects of Organophosphorus Pesticides on the Growth of Microcystis aeruginosa and Uptake of the Phosphorus Forms - P.-J. Zhou; H. Shen; J. Lin; L.-R. Song; Y.-D. Liu; Z.-B. Wu (Bulletin of Environmental Contamination and Toxicology, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Pilot point temperature regulation for thermal lesion control during ultrasound thermal therapy - H. -L. Liu; Y. -Y. Chen; J. -Y. Yen; W. -L. Lin (Medical & Biological Engineering & Computing, 2004)

Elevated Exposure to Nitrogen Dioxide During Food Preparation: Results from a Cooking Laboratory - T.-S. Lin; Y.-L. Huang (Bulletin of Environmental Contamination and Toxicology, 2004)

Detection and classification of allexiviruses from garlic in China - J. Chen; H.-Y. Zheng; J. F. Antoniw; M. J. Adams; J.-P. Chen; L. Lin (Archives of Virology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

QTLs for Na+ and K+ uptake of the shoots and roots controlling rice salt tolerance - H. X. Lin; M. Z. Zhu; M. Yano; J. P. Gao; Z. W. Liang; W. A. Su; X. H. Hu; Z. H. Ren; D. Y. Chao (Theoretical and Applied Genetics, 2004)

Causes of spatial patterns of dead trees in forest fragments in Illinois - Y. Lin; Melissa L. Hulting; Carol K. Augspurger (Plant Ecology, 2004)

Application of a ?Big-Tree? model to regional climate modeling: a sensitivity study - X.-M. Zeng; M. Zhao; R.-C. Yu; N.-S. Lin; Y.-Q. Zheng; L.-J. Zhang; R.-J. Zhang (Theoretical and Applied Climatology, 2003)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Fine linkage mapping enables dissection of closely linked quantitative trait loci for seed dormancy and heading in rice - Y. Takeuchi; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Evidence for the existence of some dissociation in an otherwise strong linkage disequilibrium between mitochondrial and chloroplastic genomes in Cyclobalanopsis glauca - T.‐P. Lin; W.‐J. Chuang; S. S. F. Huang; S.‐Y. Hwang (Molecular Ecology, 2003)
Variations in mitochondrial DNA in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. were studied in 140 trees from 32 populations collected from within the tree's natural range. By sequencing two mitochondrial DNA intron fragments ( nad 4/3 ‐nad 4/4r and nad 7/2 ‐nad 7/3r), we revealed a total of 1788 bp and five polymorphic sites which allowed us to distinguish six mitotypes. The mitochondrial DNA markers provided replicated data to support population phylogeographical scenarios suggested previously using chloroplastic DNA markers. The gene genealogical tree of mitochondrial DNA was partially congruent with the chloroplastic DNA tree owing to the slower mutation rate and different mutational direction. Significant linkage disequilibrium existed between the two organellar genomes. Further paring analyses between fragments synthesized using different primers, accompanied by exclusion of polymorphic sites, showed that the random association could be attributed specifically to one of the polymorphic sites of the pet G‐ trn P fragment of the chloroplastic genome, and the three polymorphic sites of the nad 4/3‐ nad 4/4r fragment of the mitochondrial genome. The former was inferred to derive from paternal leakage, and the latter from recurrent mutation. These polymorphic sites were also responsible for uncoupling of the combined gene tree of mitotype and chlorotype. In conclusion, specific fragments found in this study contribute to the incomplete congruence of the two organellar lineages that otherwise associate well phylogeographically.

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

Detection ofBurkholderia pseudomallei in rice fields with PCR-based technique - C. M. Kao; S. C. Chen; Y. S. Chen; H. M. Lin; Y. L. Chen (Folia Microbiologica, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

IDENTIFICATION AND AUTHENTICATION OF ANIMAL CELL CULTURE BY POLYMERASE CHAIN REACTION AMPLIFICATION AND DNA SEQUENCING - MERRY Y. LIU; SEH-CHING LIN; HSI LIU; FRANCISCO CANDAL; ABBAS VAFAI (In Vitro Cellular & Developmental Biology - Animal, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

Effect of rice-glycerol complex medium on the production of lovastatin byMonascus ruber - Y. N. Chang; Y. C. Lin; C. C. Lee; B. L. Liu; Y. M. Tzeng (Folia Microbiologica, 2002)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Biological Monitoring of Environment Exposure to Safrole and the Taiwanese Betel Quid Chewing - M. J. W. Chang; C. Y. Ko; R. F. Lin; L. L. Hsieh (Archives of Environmental Contamination and Toxicology, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Some recent advances in the theory of random vibration - Lin Y. (The Science of Nature, 2002)

Modulation of calcium balance in tilapia larvae ( Oreochromis mossambicus ) acclimated to low-calcium environments - Chou M.-Y.; Lu F.-I.; Lin H.-C.; Hwang P.-P.; Yang C.-H. (Journal of Comparative Physiology B, 2002)

Stopped-flow kinetic study of the peroxidase reactions of mangano-microperoxidase-8 - Hui-Chun Yeh; Chia-Huei Yu; Jinn-Shyan Wang; Suei-Tein Chen; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Plasmids carrying cloned fragments of RF DNA from the filamentous phage φLf can be integrated into the host chromosome via site-specific integration and homologous recombination - N.-T. Lin; R.-Y. Chang; S.-J. Lee; Y.-H. Tseng (Molecular Genetics and Genomics, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Stopped-flow kinetic study of the H2O2 oxidation of substrates catalyzed by microperoxidase-8 - Hui-Chun Yeh; Jinn-Shyan Wang; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

A natural-gradient field tracer test for evaluation of pollutant-transport parameters in a porous-medium aquifer - Y. Yang; X. Lin; T. Elliot; R. Kalin (Hydrogeology Journal, 2001)

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Characterization of a SINE species from vicuna and its distribution in animal species including the family Camelidae - Z. Lin; O. Nomura; T. Hayashi; Y. Wada; Hiroshi Yasue (Mammalian Genome, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Effects of Laundering upon the Removal of Atrazine and Metolachlor from Cotton, Cotton/Polyester, and Polyester Fabrics Treated with Fluorochemical Finishes - A. Shaw; Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Sampling efficiency of a modified closed-face cassette sampler for airborne toluene diisocyanate determination - I.-F. Mao; M.-L. Chen; Y.-C. Lin (International Archives of Occupational and Environmental Health, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part III: 6 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part II: 48-6 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Mesoscale simulations of dynamical factors discriminating between a tornado outbreak and non-event over the southeast US Part I: 84-48 hour precursors - J. M. Egentowich; M. L. Kaplan; Y.-L. Lin; A. J. Riordan (Meteorology and Atmospheric Physics, 2000)

Photodegradation of the Herbicides Butachlor and Ronstar Using Natural Sunlight and Diethylamine - Y. J. Lin; C. Lin; K. J. Yeh; A. Lee (Bulletin of Environmental Contamination and Toxicology, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Flavonoids as inducers of extracellular proteins and exopolysaccharides of Sinorhizobium fredii - C. C. Lin; Y. C. Chen; S. C. Song; L. P. Lin (Biology and Fertility of Soils, 1999)

Compression studies of gibbsite and its high-pressure polymorph - E. Huang; J.-F. Lin; J. Xu; T. Huang; Y.-C. Jean; H.-S. Sheu (Physics and Chemistry of Minerals, 1999)

The Stability and Existence Condition of Nonlinear Travelling Wave Solution in Basic Uniform Flow - Y. Xu; Z. Lin; R. Dang (Meteorology and Atmospheric Physics, 1999)

Glove Permeation Tests Using Novel Microchemical Techniques for 2,4-Dichlorophenoxyacetic Acid (2,4-D) Derivatives - Y.-W. Lin; S. S. Que Hee (Archives of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Localizations of NS3 and E proteins in mouse brain infected with mutant strain of Japanese encephalitis virus - J. J. Wang; C. L. Liao; C. I. Yang; Y. L. Lin; C. T. Chiou; L. K. Chen (Archives of Virology, 1998)

RFLP mapping of QTLs conferring salt tolerance during germination in an interspecific cross of tomato - M. R. Foolad; F. Q. Chen; G. Y. Lin (Theoretical and Applied Genetics, 1998)

Induction of apoptosis and secondary necrosis by infectious pancreatic necrosis virus in fish embryonic cells - J‐R Hong; T‐L Lin; Y‐L Hsu; J‐L Wu (Journal of Fish Diseases, 1998)
Infectious pancreatic necrosis virus (IPNV) causes an acute, contagious disease in a number of economically important fish species (Pilcher & Fryer 1980). It is a member of the Birnaviridae (Brown 1986). In this study, the present authors first characterized the process of fish cell damage caused by IPNV infection in cultured cells, and found that it induced fragmentation of chromosomal DNA into oligonucleosomes and also caused nuclear fragmentation by secondary necrosis.

Fine mapping of quantitative trait loci Hd-1, Hd-2 and Hd-3, controlling heading date of rice, as single Mendelian factors - T. Yamamoto; Y. Kuboki; S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

A SINE species from hippopotamus and its distribution among animal species - O. Nomura *, Z.-H. Lin; Not Available Not Available; Y. Wada; H. Yasue (Mammalian Genome, 1998)

Mapping quantitative trait loci controlling seed dormancy and heading date in rice, Oryza sativa L., using backcross inbred lines - S. Y. Lin; T. Sasaki; M. Yano (Theoretical and Applied Genetics, 1998)

A detailed characterization of the effects of four cannabinoid agonists on operant lever pressing - D. Carriero; J. Aberman; S. Y. Lin; A. Hill; A. Makriyannis; J. D. Salamone (Psychopharmacology, 1998)

Changes in nitric oxide synthase isoforms in the spinal cord of rat following induction of chronic arthritis - J. Wu; Q. Lin; Y. Lu; W. D. Willis; K. N. Westlund (Experimental Brain Research, 1998)

Mapping quantitative trait loci associated with regeneration ability of seed callus in rice, Oryza sativa L. - F. Taguchi-Shiobara; S. Y. Lin; K. Tanno; T. Komatsuda; M. Yano; T. Sasaki; S. Oka (Theoretical and Applied Genetics, 1997)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Molecular analysis of survival motor neuron (SMN) and neuronal apoptosis inhibitory protein (NAIP) genes of spinal muscular atrophy patients and their parents - J.-G. Chang; Yuh-Jyh Jong; Shuan-Pei Lin; Bing-Wen Soong; Chang-Hai Tsai; T.-Y. Yang; Chih-Peng Chang; Wen-Shin Wang (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Qualitative and Quantitative Analysis of Diazinon in Fabric Exposed to Various Simulated Sunlight and Humidity Conditions - A. Shaw; Y. J. Lin; E. Pfeil (Bulletin of Environmental Contamination and Toxicology, 1997)

Bcl-2 blocks peroxynitrite-induced apoptosis in HL-60 cells, an association with reactive oxygen species - K.-T. Lin; J.-Y. Xue; P. Y.-K. Wong (Inflammation Research, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Sweet potato (Ipomoea batatas) trypsin inhibitors expressed in transgenic tobacco plants confer resistance against Spodoptera litura - K.-W. Yeh; M.-I. Lin; S.-J. Tuan; Y.-M. Chen; C.-J. Lin; S.-S. Kao (Plant Cell Reports, 1997)

Phylogenetic analysis of feline immunodeficiency virus isolated from cats in Taiwan - G. Inada; T. Miyazawa; Y. Inoshima; M. Kohmoto; Y. Ikeda; C. -H. Liu; J. A. Lin; T. -F. Kou; T. Mikami (Archives of Virology, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

The epidemiology and surveillance of blood lead in Taiwan (R.O.C.): A report on the PRESS-BLL project - T.-N. Wu; Chen-Yang Shen; Saou-Hsing Liou; Guang-Yang Yang; K.-N. Ko; Show-Lin Chao; Chao-Chun Hsu; P.-Y. Chang (International Archives of Occupational and Environmental Health, 1997)

Diversity associated with the second expressed H L A - D R B locus in the human population - FuMeei Robbins; Carolyn Katovich Hurley; Ting Tang; Hanlong Yao; Y. S. Lin; Judy Wade; Nancy Goeken; Robert J. Hartzman (Immunogenetics, 1997)

The bcl-2 family member, Bcl2a1, maps to mouse Chromosome 9 and human Chromosome 15 - Elaine Y. Lin; Christine A. Kozak; Amos Orlofsky; Michael B. Prystowsky (Mammalian Genome, 1997)

Physical mapping of four RAPDs in the B chromosome of maize - B.-Y. Lin; H.-P. Chou (Theoretical and Applied Genetics, 1997)

Assignment of DNA markers to Nicotiana sylvestris chromosomes using monosomic alien addition lines - D. F. Suen; C. K. Wang; R. F. Lin; Y. Y. Kao; F. M. Lee; C. C. Chen (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

A preliminary study of the formation of precipitation systems under undisturbed conditions during TAMEX - C. -S. Chen; C. -Y. Lin (Meteorology and Atmospheric Physics, 1997)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Capsid protein of cucumber mosaic virus accumulates in the nuclei and at the periphery of the nucleoli in infected cells - N. -S. Lin; C. -E. Hsieh; Y. -H. Hsu (Archives of Virology, 1996)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Complete genomic RNA sequences of cucumber mosaic virus strain NT9 from Taiwan - Y. -H. Hsu; C. -W. Wu; B. -Y. Lin; H. -Y. Chen; M. -F. Lee; C. -H. Tsai (Archives of Virology, 1995)

Estimation of selected phenols in drinking water with In situ acetylation and study on the DNA damaging properties of polychlorinated phenols - Y.-J. Wang; J.-K. Lin (Archives of Environmental Contamination and Toxicology, 1995)

A long lytic cycle in filamentous phage Cf1tv infectingXanthomonas campestris pv.citri - T. -T. Kuo; C. -C. Chiang; S. -Y. Chen; J. -H. Lin; J. -L. Kuo (Archives of Virology, 1994)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Stimulation of thymidine kinase activity in baculovirus infected cells is not due to a virus-coded enzyme - X. Wang; W. Xie; Q. Long; D. He; G. Lin; Y. Pang; Z. Pu (Archives of Virology, 1992)

A new typing method for the avian infectious bronchitis virus using polymerase chain reaction and restriction enzyme fragment length polymorphism - Z. Lin; A. Kato; Y. Kudou; S. Ueda (Archives of Virology, 1991)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)

A parallel algorithm for estimating the secondary structure in ribonucleic acids - Y. Takefuji; C. W. Lin; K. C. Lee (Biological Cybernetics, 1990)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Primary structure of the marmoset (Saguinus fuscicollis) hemoglobin. I. Use of tryptic maleylated peptides in the solubilization and sequence elucidation of the ?- and ?-chains - K. D. Lin; Y. K. Kim; A. I. Chernoff (Biochemical Genetics, 1976)